Developing device
The developing device addresses the issues of surface contamination and high voltage in charge injection charging methods by using a toner carrier with controlled electrical properties and interfacial conductive phenomena, ensuring effective toner charge and high-quality image formation.
Patent Information
- Application Number
- JP2020191173
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-17
- Publication Date
- 2024-12-16
- Estimated Expiration
- 2040-11-17
AI Technical Summary
Conventional charge injection charging methods using conductive toner and high-resistance toner carriers in image forming apparatuses face issues with increased electrostatic adsorption force leading to surface contamination of the toner carrier, large electrostatic energy loss, and decreased toner charge amount, along with high applied voltages.
A developing device with a toner carrier having specific electrical properties, including volume resistivity and capacitance ratios, and a toner regulating member, which controls interfacial conductive phenomena to maintain toner charge and prevent surface contamination, using a two-layer toner carrier structure with different dielectric relaxations to manage charge injection and retention.
The solution achieves both conductivity and charge retention of the toner, suppressing the increase in applied voltage during charge injection, resulting in high-quality image formation.
Smart Images

Figure 0007599920000009 
Figure 0007599920000010 
Figure 0007599920000011
Abstract
Description
[Technical field]
[0001] The present disclosure relates to image forming apparatuses such as copiers and printers. In particular, the present invention relates to a conductive toner that exhibits electrical conductivity under an applied voltage equal to or lower than the dielectric strength electric field of air, and to a developing device having a toner carrier that carries the toner and a toner regulating member that regulates the toner. [Background technology]
[0002] In recent years, the fields in which electrophotographic image forming apparatuses are used have become more diverse, ranging from printers and copiers to commercial printing machines. Accordingly, there is a demand for image forming apparatuses to operate at higher speeds and with higher quality. The developing device built into the conventional image forming apparatus uses a friction charging method, and it has been pointed out that the time constant related to the toner charge rise characteristic is large, and the toner charge amount distribution becomes broad. In order to solve these problems, a charge injection charging method using a conductive toner has been proposed. As a developing device using the charge injection charging method, the following has been disclosed.
[0003] For example, Patent Document 1 proposes charging the toner both by charge injection from a regulating blade and by contact frictional charging with a toner carrier. Specifically, the DC resistance of the pressure-molded toner pellet is 1×10 7 More than 1×10 9 (Ω cm) or less, and the capacitance is 1.0×10 -12 More than 1.5 x 10 -11 The toner has the following electrical characteristics (F). Also, Patent Document 2 discloses a conductive toner, a toner carrier, and a developing system using a charge injection charging method. Figure 19 on page 27 describes the electrical characteristics of the conductive toner. The toner exhibits a nonlinear current-voltage characteristic and is charged at a field strength of 8×10 3 (V / cm) 10 16(Ω cm), and has an electric field strength of 7×10 4 (V / cm) 10 9 The toner has a conductivity of 10 11 The device is provided with a high-resistance layer having a volume resistivity of 1000 Ω·cm or higher. As a specific toner carrier, it is described in Example 1 that an aluminum pipe that has been anodized is used, and in Example 2 that a 12 μm thick PET film is wrapped around the toner carrier. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2008-58874 A [Patent Document 2] JP 2005-331782 A [Non-patent literature]
[0005] [Non-Patent Document 1] Surface Science Vol. 29, No. 2, pp. 105-113, Iwamoto et al. "Charge accumulation and carrier transport at organic semiconductor / insulator interfaces", Section 2.1 "Interface charge accumulation due to the Maxwell-Wagner effect" Summary of the Invention [Problem to be solved by the invention]
[0006] The conductive toner described in Patent Document 1, when combined with a high-resistance toner carrier exhibiting insulating dielectric properties, increases the electrostatic adsorption force of the toner carrier, making the toner carrier more susceptible to surface contamination. It has been found that in combination with a carrier, the electrostatic energy loss of the toner increases, and the amount of charge of the toner decreases. The conductive toner described in Patent Document 2 exhibits nonlinear voltage-current characteristics, and there exists a threshold voltage at which the toner changes from insulating to conductive. From these characteristics, the desired injection field strength that indicates the conductivity of the toner is 1×10 5 (V / cm) is required, and it was found that the voltage applied between the toner carrier and the regulating blade becomes high. In addition, the surface layer of the toner carrier becomes highly resistive, so the electrostatic adsorption force of the toner carrier increases, making the surface of the toner carrier more susceptible to contamination.
[0007] As described above, it is difficult for the conductive toner in the conventional charge injection charging method to maintain the toner charge amount while preventing the surface contamination of the toner carrier. Furthermore, the voltage applied to obtain a predetermined toner charge amount becomes high. The present disclosure provides a developing device that can achieve both the conductivity and charge retention of a conductive toner in a charge injection charging method, can suppress an increase in the applied voltage during charge injection, and can achieve high-quality image formation. [Means for solving the problem]
[0008] The present disclosure relates to a developing device having a toner, a toner carrier that carries the toner, and a toner regulating member that contacts the toner carrier and regulates the toner carried by the toner carrier, the toner carrier has a core metal, The volume resistivity of the toner determined by impedance measurement is 1.0×10 10 Ω cm or more 1.0×10 14 Ω cm or less, The toner carrier Measured between the core metal and the surface of the toner carrier using a measuring electrode with a diameter of 0.65 mm. In impedance measurements, several elementary processes are observed. The toner carrier surface per unit area Between the core Volume resistance Rdr is 5.0×10 5 Ω / cm 2 Above 2.0×10 8 Ω / cm 2 is as follows: The toner carrier surface per unit area Between the core Capacitance Cdr is 300pF / cm 2 More than 900pF / cm2 is as follows: A measurement electrode with a diameter of 10 mm was used. The capacitance per unit area of the toner, calculated from the volume resistivity and dielectric constant of the toner obtained by impedance measurement, is expressed as Ctn (pF / cm) using a parallel plate capacitor model with a thickness 1.5 times the weight average particle diameter D4 of the toner obtained by the electrical detection zone method. 2 ), and the volume resistance per unit area of the toner is Rtn (Ω / cm 2 ), The present invention relates to a developing device that satisfies the following formulas (1) and (2). 1.5 ≦(Cdr / Ctn)≦4.5 (1) 1.0×10 -4 ≦(Rdr / Rtn)≦ 1.0 (2) Effect of the Invention
[0009] According to the present disclosure, it is possible to provide a developing device that can achieve both the conductivity and charge retention of a conductive toner in a charge injection charging method, can suppress an increase in the applied voltage during charge injection, and can achieve high-quality image formation. [Brief description of the drawings]
[0010] [Figure 1] Example of a cross-sectional view of a process cartridge incorporating a developing unit [Diagram 2] Example of a cross-sectional view of a developing roller [Diagram 3] Example of electrical characteristics of developing roller DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The expressions "XX or more and YY or less" or "XX to YY" representing a numerical range mean a numerical range including the endpoints, that is, the lower limit and the upper limit, unless otherwise specified.
[0012] As a result of intensive research, the present inventors have found that the following developing device can provide a developing device capable of controlling the interfacial conductive phenomenon and achieving high-quality image formation. The present disclosure relates to a developing device having a toner, a toner carrier that carries the toner, and a toner regulating member that contacts the toner carrier and regulates the toner carried by the toner carrier, The volume resistivity of the toner determined by impedance measurement is 1.0×10 10 Ω cm or more 1.0×10 14 Ω cm or less, In the toner carrier, a plurality of elementary processes are observed in the impedance measurement, The volume resistance value Rdr per unit area of the toner carrier is 5.0×10 5 Ω / cm 2 Above 2.0×10 8 Ω / cm 2 is as follows: The capacitance Cdr per unit area of the toner carrier is 300 pF / cm 2 More than 900pF / cm 2 is as follows: The capacitance per unit area of the toner, calculated from the volume resistivity and dielectric constant of the toner obtained by impedance measurement, is expressed as Ctn (pF / cm) using a parallel plate capacitor model with a thickness 1.5 times the weight average particle diameter D4 of the toner obtained by the electrical detection zone method. 2 ), and the volume resistance per unit area of the toner is Rtn (Ω / cm 2 ), The present invention relates to a developing device that satisfies the following formulas (1) and (2). 1.5 ≦(Cdr / Ctn)≦4.5 (1) 1.0×10 -4 ≦(Rdr / Rtn)≦ 1.0 (2)
[0013] The inventors speculate as follows about the mechanism by which the above configuration enables the retention of toner charge amount and the prevention of surface contamination of the toner carrier in the charge injection charging method, while also preventing the application voltage from becoming too high during charge injection. First, the parameters for controlling the electrical characteristics of conductive toner that allows the charge injection charging method to be applied will be considered. The electrical properties of typical dielectric materials include dielectric constant, volume resistivity, and electrical conductivity, and the electrical properties such as capacitance, resistance, and conductance (conductivity) are determined by the electrical properties and geometric shape. Regarding the dielectric constant, which is an electrical property of toner, the range in which the dielectric constant can be controlled by the toner material and manufacturing conditions is small. For this reason, the toner capacitance Ctn can be controlled by changing the toner particle size and the material composition of the toner.
[0014] On the other hand, the volume resistivity, which is an electrical property of the toner, can be controlled over a wide range by using a material such as a metal oxide as a conductive filler or charge trap site near the toner surface. In addition, the control amount of the relative dielectric constant at this time is small compared to the volume resistivity. For this reason, the volume resistivity Rtn of the toner can be controlled over a wide range by controlling the vicinity of the toner surface, making it possible to obtain a predetermined conductive toner. However, imparting electrical conductivity to a toner results in electrostatic energy loss, and it has been difficult to achieve both electrical conductivity and charge retention properties at the same time.
[0015] Therefore, the present inventors have focused on the toner carrier and the interfacial conductivity phenomenon that occurs when toner and a toner carrier are combined, and have referred to the following documents. According to the description in "Charge accumulation and carrier transport at organic semiconductor / insulator interfaces" by Iwamoto et al. in Section 2.1 "Interfacial charge accumulation due to the Maxwell-Wagner effect" (hereinafter also referred to as Reference A) in Surface Science Vol. 29, No. 2, pp. 105-113, there is a basic rule that "charge accumulation at an interface occurs when the relaxation times (dielectric relaxation) of the two substances are different." It is written that the phenomenon whereby electric charges accumulate at an interface according to this law (interface polarization phenomenon) is the Maxwell-Wagner effect. Furthermore, it is written that the effect applies whether the electric charges are collected at the interface from within the bulk of the Si semiconductor or flow in from an electrode, regardless of the route by which the accumulated electric charges flow into the interface.
[0016] According to Literature A, a toner carrier consisting of two layers, a conductive elastic layer and a surface layer, can form an interface with different dielectric relaxation by controlling the resistance and capacitance of each. Then, charges are accumulated at the interface (interface polarization charge) due to the Maxwell-Wagner effect (interface polarization phenomenon). This accumulated charge also exists when mobile ions exist or when a current flows through the toner carrier.
[0017] In this case, if the electric charge accumulated at the interface (interface polarization charge) generates a reverse electric field in the opposite direction to the electric field applied to the toner carrier, the electric field strength inside the toner carrier bulk decreases and the volume resistance increases. It was thought that this could potentially suppress the current flowing through the toner carrier. Furthermore, when the volume resistance Rdr of the toner carrier is smaller than the volume resistance Rtn of the toner (corresponding to the above formula (2)), the volume resistance Rdr of the toner carrier becomes the rate-limiting condition for the current flowing through the toner and the toner carrier.
[0018] In addition, the surface layer of the toner carrier induces charges in response to the charges (interface polarization charges) accumulated at the interface between the conductive elastic layer and the surface layer of the toner carrier, thereby increasing the surface charge of the toner carrier in contact with the toner. Similarly, according to Document A, it is believed that a similar interfacial polarization phenomenon can be generated at the interface between the toner and the toner carrier, and the charge amount of the toner can be improved.
[0019] This paper describes the electrical properties of a toner carrier that consists of two layers, a conductive elastic layer and a surface layer, which have different dielectric relaxation properties. The conductive elastic layer and surface layer that compose the toner carrier are assumed to be an electric circuit model in which the respective RC parallel circuits are connected in series. Here, the fact that the dielectric relaxation of each layer is different indicates that the frequency dependence of the electrical AC characteristics is different. In general, by using an analysis method called impedance spectroscopy, it is possible to separate and identify the elementary processes of the RC parallel circuit model caused by the conductive elastic layer and the elementary processes of the RC parallel circuit model caused by the surface layer. Therefore, the fact that the toner carrier is composed of two layers with different dielectric relaxation, which is a necessary condition for the occurrence of the interfacial polarization phenomenon, indicates that there are two elementary processes that can be distinguished from the impedance characteristics. Conversely, when the dielectric relaxation approaches, it becomes difficult to separate and identify the elementary processes using impedance spectroscopy. It is necessary that a plurality of elementary processes are observed in the toner carrier. The number of elementary processes is preferably 2. The presence of a plurality of elementary processes in the toner carrier indicates that an interfacial polarization charge exists at the interface between the conductive elastic layer and the surface layer constituting the toner carrier.
[0020] In addition, the difference in dielectric relaxation between the toner and the toner carrier was expressed using electrical characteristics such as resistance and capacitance, and the above-mentioned relational expressions (1) and (2) were derived. Here, the electrical characteristics of the toner and the toner carrier will be described. Usually, the thickness of the toner that has passed through the regulating member is adjusted to a toner thickness equivalent to 1.5 times the toner particle diameter, which is the amount of toner required to obtain a predetermined image density. From this, the electrical properties of the toner are calculated using the volume resistivity and relative dielectric constant obtained by impedance measurement, and a parallel plate capacitor model with a thickness 1.5 times the weight average particle diameter D4 of the toner obtained by the electrical detection zone method.
[0021] The capacitance per unit area of the toner is Ctn (pF / cm 2 ), and the volume resistance per unit area is Rtn (Ω / cm 2 ) is defined as The toner is a conductive toner that exhibits electrical conductivity when a voltage is applied that is equal to or lower than the electric field strength of the dielectric strength of air, so that charge injection by application of a low voltage is possible. Specifically, to improve the charge rise characteristics, the time constant is reduced to 1×10 1 0 Ω cm or more 1×10 14 The toner has a volume resistivity of Ω·cm or less.
[0022] The capacitance per unit area, Cdr (pF / cm), obtained by measuring the impedance of the toner carrier that carries the toner is 2 ), and the volume resistance per unit area is Rdr (Ω / cm 2 The volume resistivity Rdr is defined as 5.0×10 5 Ω / cm 2 Above 2.0×10 8 Ω / cm 2 The following is the result. When the volume resistance value Rdr of the toner carrier is large, the charge retention function is improved, and the electrostatic adsorption force on the surface of the toner carrier increases, which may cause surface contamination of the toner carrier and make it difficult to form a toner layer of uniform thickness on the toner carrier, which may lead to phenomena such as poor regulation. Therefore, the volume resistance value Rdr per unit area of the toner carrier is 2.0×10 8 Ω / cm 2 It needs to be as follows. In addition, when the volume resistivity Rdr of the toner carrier is small, the charge retention function of the toner carrier is reduced due to electrostatic energy loss, and the toner carrier is unable to retain the charge. Therefore, the volume resistivity Rdr per unit area capable of retaining the charge is 5.0×10 5 Ω / cm 2 It needs to be more than that. The volume resistivity Rdr is preferably 1.0×10 7 Ω / cm 2 More than 1.8 x 10 8 Ω / cm 2 The following is the result. The volume resistivity Rdr can be controlled by the formulation of the conductive paint and the surface layer paint. The capacitance Cdr per unit area of the toner carrier is 300 pF / cm 2 More than 900pF / cm 2 When Cdr is within the above range, the charge rise characteristics of the toner can be improved. The capacitance Cdr is preferably 350 pF / cm 2 More than 500pF / cm 2The capacitance Cdr can be controlled by the formulation of the conductive paint and the surface layer paint.
[0023] Next, the electrical characteristics (charge rise characteristics) of the toner carrier on which the conductive toner is laminated will be described. Hereinafter, we will assume a transient response characteristic when a step voltage is applied (hereinafter referred to as the step response characteristic) as an electrical model in which a voltage is applied to toner stacked on a toner carrier as it passes through a regulating member, causing injection charging. At the moment when the voltage Vin is applied between the toner and the toner carrier, an inrush current flows, the toner capacitance Ctn and the toner carrier capacitance Cdr are charged, and the toner voltage Vtn and the toner carrier voltage Vdr are determined. At this time, the toner voltage Vtn is Vtn = Cdr / (Cdr+Ctn) × Vin and the toner carrier voltage Vdr is Vdr=Ctn / (Cdr+Ctn)×Vin It becomes.
[0024] That is, the distribution ratio of the applied voltage Vin between the toner voltage Vtn and the toner carrier voltage Vdr immediately after the application of the voltage Vin is determined according to the electrostatic capacitance ratio between the toner and the toner carrier. Therefore, by setting the ratio of the capacitance Cdr of the toner carrier to the capacitance Ctn of the toner (Cdr / Ctn) to 1.5 to 4.5, the distribution ratio of the toner voltage Vtn to the applied voltage Vin can be controlled to 0.6 to 0.8, thereby improving the toner charge rise characteristic.
[0025] Next, the step response characteristics of the toner voltage Vtn after the voltage Vin is applied and the toner voltage Vtn and the distribution voltage for the applied voltage Vin of the toner carrier Vdr are determined will be described. The step response characteristic after the toner voltage Vtn is determined is as follows: These can be broadly divided into cases where the fluctuation is small, cases where the fluctuation is increasing, and cases where the fluctuation is small.
[0026] The step response characteristic is determined by the time constant (τdr=Rdr×Cdr) of the toner carrier, which is determined by the volume resistance Rdr and capacitance Cdr of the toner carrier, the volume resistance Rtn of the toner, and the volume resistance Rdr of the toner carrier. Basically, the toner voltage Vtn converges to Rtn / (Rdr+Rtn)×Vin, where Rtn is the volume resistance of the toner and Rdr is the volume resistance of the toner carrier.
[0027] First, the condition for the toner voltage Vtn not to change is when the relational expression Cdr / (Cdr+Ctn)=Rtn / (Rdr+Rtn) is satisfied. When this relational expression is expressed using the above relational expressions (1) and (2), the condition for (Cdr / Ctn)=1 / (Rdr / Rtn) is satisfied. From the above relational expression, when (Cdr / Ctn)>1 / (Rdr / Rtn), the toner voltage Vtn decreases, and conversely, when (Cdr / Ctn)<1 / (Rdr / Rtn), the toner voltage Vtn increases, showing a step response characteristic.
[0028] Furthermore, the step response characteristic of the toner voltage Vtn increasing is attributed to the time constant τdr of the toner carrier, which is Rdr×Cdr. In other words, in order to improve the toner charge amount and the rising characteristic in the electrophotographic process, it is more preferable that the time constant τdr of the toner carrier is equal to or shorter than the time it takes for the toner to pass through the regulating member. As described above, in order to maintain and improve the charging characteristics of the toner, it is necessary that (Cdr / Ctn)≦1 / (Rdr / Rtn). As a specific guideline, it is preferable that (Cdr / Ctn) in the relational expression (1) is 1.0 or more, and (Rdr / Rtn) in the relational expression (2) is 1.0 or less.
[0029] The case where (Rdr / Rtn) in the relational expression (2) exceeds 1.0, which is outside the above necessary condition, will be described. In this region, if the volume resistance value Rdr of the toner carrier is high, the electrostatic adsorption force of the toner carrier increases, and the possibility of surface contamination increases. Also, if the volume resistance value Rtn of the toner is low, the amount of charge of the toner decreases. Therefore, (Rdr / Rtn) must be 1.0 or less, and considering the charge decay characteristics, it is preferable that it is 0.5 or less.
[0030] In the formula (2), (Rdr / Rtn) is 1.0×10 -4 We will now discuss the case where the value is less than In this region, if the toner volume resistance Rtn is high, charge injection charging does not work, frictional charging becomes dominant, and the toner is easily charged up. Also, if the toner carrier volume resistance Rdr is low, the toner carrier capacitance Cdr also decreases, and the toner charge rise characteristic decreases. (Rdr / Rtn) is preferably 1.0×10 -3 That's all.
[0031] The present disclosure focuses on controlling electrical characteristics based on the interfacial polarization phenomenon between a toner and a toner carrier, thereby achieving both charge injection properties and charge retention properties. In this case, if (Cdr / Ctn) in the relational expression (1) is less than 1.5, the dielectric relaxation characteristics of the toner and the toner carrier cannot be differentiated in relation to (Rdr / Rtn) in the relational expression (2), making it difficult to control the interfacial polarization phenomenon, reducing the toner charge amount and making it impossible to maintain a sufficient charge amount.
[0032] When (Cdr / Ctn) exceeds 4.5, it means that there is a difference in the charge retention ability between the toner and the toner carrier. Therefore, the interface where the difference in charge retention ability is large is subject to the mirror effect. It becomes difficult to retain the charge due to thermionic emission, tunnel effect, space charge limited current, etc. As a result, leakage current occurs, making it difficult to retain the charge of the toner. (Cdr / Ctn) is preferably 1.7 or more and 3.4 or less.
[0033] As described above, by controlling the interfacial polarization phenomenon at the internal interface of the toner carrier and the interfacial polarization phenomenon at the interface between the toner carrier and the toner, it is possible to achieve both electrical conductivity and charge retention of the toner. Furthermore, since the toner and the toner carrier have electrical conductivity, it is possible to prevent the applied voltage from becoming too high when injecting electric charges.
[0034] Next, the composition of the toner used in the developing device will be described in detail below, but the toner is not limited to the following. The volume resistivity of the toner determined by impedance measurement is 1.0×10 10 Ω cm or more 1.0×10 14 Ω·cm or less. When the volume resistivity of the toner is in the above range, it is possible to both inject electric charge into the toner and retain the injected electric charge. 10 If the resistivity is less than Ω·cm, even if the relational expressions (1) and (2) are satisfied, leakage of charge from the toner is likely to occur, making it difficult to maintain the charge amount. On the other hand, the volume resistivity is 1.0×10 14 When the volume resistivity exceeds 1.0×10 Ω·cm, the charge injection into the toner does not substantially occur, and the effect of the present invention cannot be obtained. 11 Ω cm or more 1.0×10 14 It is preferable that the resistivity is Ω·cm or less. The volume resistivity can be controlled by controlling the volume resistivity of a material disposed near the toner surface or inside the toner, etc. Among these, it is preferable to control the volume resistivity of the toner by a material disposed near the toner surface, since the amount of material required to control the volume resistivity of the toner is small and the effect on the fixability of the toner is small.
[0035] The relative dielectric constant of the toner is preferably 1.50 or more and 3.00 or less. When the relative dielectric constant is in the above range, the saturated charge amount of the toner falls within a preferred range. The relative dielectric constant is more preferably 1.80 or more and 2.50 or less. The relative dielectric constant can be controlled by controlling the relative dielectric constant of the material disposed on the toner surface or inside the toner.
[0036] The weight average particle diameter (D4) of the toner is preferably 3.0 μm or more and 10.0 μm or less, and more preferably 4.5 μm or more and 8.0 μm or less. When D4 is in the above range, the charge distribution is easily controlled, and at the same time, the latent image reproducibility is excellent, so that a high-quality image can be obtained. In addition, since the capacitance value Ctn per unit area of the toner is determined by the relative dielectric constant of the toner and the thickness of the toner layer, it becomes easier to satisfy the relational expression (2) by controlling the D4 of the toner in accordance with the capacitance Cdr per unit area of the toner carrier.
[0037] The toner has toner particles. It is preferable to arrange a material having a higher electrical conductivity than the toner particles on the surface of the toner particles. For example, the material may be fine particles A containing a compound containing a metal element (hereinafter, simply referred to as metal compound fine particles A). For example, it is preferable that the toner particles have metal compound fine particles A on their surface. By having the metal compound fine particles A on the surface of the toner particles, the volume resistivity of the toner can be easily controlled, and therefore it is easy to obtain a toner that satisfies the relational expression (2). As the metal compound constituting the metal compound fine particles A, any conventionally known metal compound can be used without any particular limitation.
[0038] Specific examples include metal oxides such as titanium oxide, aluminum oxide, tin oxide, and zinc oxide; composite oxides such as strontium titanate and barium titanate; and polyvalent acid metal salts such as titanium phosphate, zirconium phosphate, and calcium phosphate. Among them, metal oxides or polyvalent metal salts are preferred from the viewpoint of structural stability and volume resistivity. In addition, polyvalent metal salts are more preferred because they have a moderate polarized structure, which makes it easy to generate induced charges due to potential differences, and because the network structure in the molecule allows smooth charge transfer, which enables more efficient injection charging. In other words, it is preferred that the toner particles have a polyvalent metal salt on their surface. When the toner particles have a shell on their surface, it is preferred that the polyvalent metal salt is present on the surface of the shell.
[0039] As the metal element, any conventionally known metal element can be used without any particular limitation. The metal compound fine particles A preferably contain at least one metal element selected from the group consisting of metal elements included in Groups 3 to 13. Metal compounds containing metal elements from Groups 3 to 13 tend to have low water absorption, and therefore the humidity dependency of charge injection properties and charge retention properties is further reduced, and stability against the usage environment can be further improved.
[0040] The Pauling electronegativity of the metal element is preferably 1.25 to 1.80, more preferably 1.30 to 1.70. When the electronegativity of the metal element is within the above range, appropriate polarization occurs in the metal part and the nonmetal part in the metal compound, enabling more efficient injection charging. The Pauling electronegativity was determined from the value given in "Chemical Handbook: Basics, 5th Revised Edition, table inside front cover, edited by the Chemical Society of Japan (2004), Maruzen Publishing."
[0041] Specific examples of the metal element include titanium (Group 4, electronegativity: 1.54), zirconium (Group 4, 1.33), aluminum (Group 13, 1.61), zinc (Group 12, 1.65), indium (Group 13, 1.78), and hafnium (Group 4, 1.30). Among these, it is preferable to use a metal that can have a valence of three or more, more preferably at least one selected from the group consisting of titanium, zirconium, and aluminum, and further preferably titanium. When a polyvalent acid metal salt is used as the metal compound, the above-mentioned metal elements can be suitably used as the metal element. Furthermore, the polyvalent acid is not particularly limited and any conventionally known polyvalent acid can be used.
[0042] The polyacid preferably contains an inorganic acid. Inorganic acids have a more rigid molecular skeleton than organic acids, and therefore the change in properties during long-term storage is small. Therefore, it is possible to obtain stable injection charging properties even after long-term storage. Specific examples of polyvalent acids include inorganic acids such as phosphoric acid (trivalent), carbonic acid (divalent), and sulfuric acid (divalent); and organic acids such as dicarboxylic acid (divalent) and tricarboxylic acid (trivalent). Specific examples of organic acids include dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, fumaric acid, maleic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, phthalic acid, isophthalic acid, and terephthalic acid; and tricarboxylic acids such as citric acid, aconitic acid, and trimellitic anhydride. Among these, at least one selected from the group consisting of inorganic acids phosphoric acid, carbonic acid, and sulfuric acid is preferred, and phosphoric acid is more preferred.
[0043] Specific examples of polyvalent acid metal salts combining the above-mentioned metal elements and polyvalent acids include titanium phosphate compounds, zirconium phosphate compounds, aluminum phosphate compounds, copper phosphate compounds, etc. Metal phosphates; metal sulfates such as titanium sulfate compounds, zirconium sulfate compounds, and aluminum sulfate compounds; metal carbonates such as titanium carbonate compounds, zirconium carbonate compounds, and aluminum carbonate compounds; and metal oxalates such as titanium oxalate compounds. Among these, since the phosphate ions cross-link metals, thereby providing high strength, and since the ionic bonds are present in the molecules, the charge build-up properties are also excellent, it is preferable that the polyvalent acid metal salt contains a metal phosphate, and it is more preferable that it contains a titanium phosphate compound.
[0044] The method for obtaining the polyvalent acid metal salt is not particularly limited, and any known method can be used. Among them, a method for obtaining the polyvalent acid metal salt by reacting a metal compound serving as a metal source with a polyvalent acid ion in an aqueous medium is preferred. As the metal source, any known metal compound can be used without particular limitation, so long as it is a metal compound that gives a polyvalent acid metal salt upon reaction with a polyvalent acid ion.
[0045] Specific examples of the metal chelates include titanium lactate, titanium tetraacetylacetonate, titanium lactate ammonium salt, titanium triethanolamine, zirconium lactate, zirconium lactate ammonium salt, aluminum lactate, aluminum trisacetylacetonate, and copper lactate; and metal alkoxides such as titanium tetraisopropoxide, titanium ethoxide, zirconium tetraisopropoxide, and aluminum trisisopropoxide. Among these, metal chelates are preferred because the reaction is easy to control and they react quantitatively with polyvalent acid ions, and lactate chelates such as titanium lactate and zirconium lactate are more preferred from the viewpoint of solubility in aqueous media. The polyvalent acid ion may be an ion of the above-mentioned polyvalent acid. When the polyvalent acid ion is added to the aqueous medium, the polyvalent acid itself may be added, or a water-soluble polyvalent acid metal salt may be added to the aqueous medium and dissociated in the aqueous medium. The content of the polyvalent acid metal salt in the toner particles is preferably from 0.01% by mass to 5.00% by mass, more preferably from 0.02% by mass to 3.00% by mass, and even more preferably from 0.05% by mass to 2.00% by mass.
[0046] The toner particles preferably have an organosilicon polymer on their surface. That is, the toner particles preferably have a toner base particle and an organosilicon polymer on the surface of the toner base particle. The organosilicon polymer is preferably an organosilicon condensate. By having an organosilicon polymer on the surface of the toner particles, and by combining it with a toner carrier having an organosilicon polymer, which will be described later, it is possible to reduce the difference in work function between the toner and the toner carrier, which makes it possible to suppress the transfer of charge due to frictional charging between the toner and the toner carrier, and to maintain a sharp charge amount distribution due to injection charging. In a typical friction charging system, the toner is charged by friction between the toner and the toner carrier. Therefore, it is common to make the friction charging easier by increasing the difference in work function between the toner and the toner carrier. On the other hand, in an injection charging system, a sharper charge amount distribution can be obtained compared to friction charging, so it is preferable to reduce the influence of friction charging.
[0047] The organosilicon polymer on the surface of the toner particles preferably forms a shell. The toner particles preferably have a shell of the toner base particles and the organosilicon polymer on the surface of the toner base particles. By having the shell, the migration of the fine particles to the toner carrier can be more suppressed compared to toners having normal silica fine particles, etc., so that it is possible to suppress the performance change of the toner carrier. Therefore, it is possible to obtain a developing device that shows good injection charging performance for a long period of time.
[0048] The organosilicon polymer can be any known organosilicon polymer without any particular limitations, and it is particularly preferred to use an organosilicon polymer having a structure represented by the following formula (I): R-SiO 3 / 2 (I) In formula (I), R represents an alkyl group (preferably having 1 to 8 carbon atoms, more preferably having 1 to 6 carbon atoms), an alkenyl group (preferably having 1 to 6 carbon atoms, more preferably having 1 to 4 carbon atoms), an acyl group (preferably having 1 to 6 carbon atoms, more preferably having 1 to 4 carbon atoms), an aryl group (preferably having 6 to 14 carbon atoms, more preferably having 6 to 10 carbon atoms), or a methacryloxyalkyl group.
[0049] Formula (I) indicates that the organosilicon polymer has an organic group and a silicon polymer portion. As a result, in the organosilicon polymer containing the structure represented by formula (I), the organic group has an affinity with the toner base particles, so that it adheres strongly to the toner base particles, and the silicon polymer portion has an affinity with the metal compound, so that it adheres strongly to the metal compound fine particles A. In this way, the organosilicon polymer has the function of adhering the toner particles and the metal compound fine particles A, so that the metal compound fine particles A can be more firmly adhered to the toner base particles. Formula (I) also indicates that the organosilicon polymer is crosslinked. The crosslinked structure of the organosilicon polymer increases the strength of the organosilicon polymer, and reduces the number of remaining silanol groups, thereby increasing hydrophobicity. This makes it possible to obtain a toner that is more durable and performs stably even in high humidity environments. In formula (I), R is preferably an alkyl group having from 1 to 6 carbon atoms, such as a methyl group, a propyl group, or a normal hexyl group, a vinyl group, a phenyl group, or a methacryloxypropyl group, and more preferably an alkyl group or a vinyl group having from 1 to 6 carbon atoms. Since organosilicon polymers having the above structure have both hardness and flexibility due to the controlled molecular mobility of the organic groups, toner deterioration is suppressed even when used over long periods of time, and excellent performance is exhibited.
[0050] The organosilicon compound for obtaining the organosilicon polymer can be any known organosilicon compound without any particular limitation, and is preferably at least one selected from the group consisting of organosilicon compounds represented by the following formula (II): R-Si-Ra 3 (II) In formula (II), each Ra independently represents a halogen atom or an alkoxy group (preferably having 1 to 4 carbon atoms, more preferably having 1 to 3 carbon atoms). Each R independently represents an alkyl group (preferably having 1 to 8 carbon atoms, more preferably having 1 to 6 carbon atoms), an alkenyl group (preferably having 1 to 6 carbon atoms, more preferably having 1 to 4 carbon atoms), an aryl group (preferably having 6 to 14 carbon atoms, more preferably having 6 to 10 carbon atoms), an acyl group or a methacryloxyalkyl group (preferably having 1 to 6 carbon atoms, more preferably having 1 to 4 carbon atoms).
[0051] Specific examples of the silane compound represented by formula (II) include trifunctional methylsilane compounds such as methyltrimethoxysilane, methyltriethoxysilane, methyldiethoxymethoxysilane, and methylethoxydimethoxysilane; trifunctional silane compounds such as ethyltrimethoxysilane, ethyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, butyltrimethoxysilane, butyltriethoxysilane, hexyltrimethoxysilane, and hexyltriethoxysilane; phenyltrimethoxysilane, phenyltriethoxysilane, and the like. trifunctional phenylsilane compounds such as isethoxysilane; trifunctional vinylsilane compounds such as vinyltrimethoxysilane and vinyltriethoxysilane; trifunctional allylsilane compounds such as allyltrimethoxysilane, allyltriethoxysilane, allyldiethoxymethoxysilane and allylethoxydimethoxysilane; γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropyltriethoxysilane, γ-methacryloxypropyldiethoxymethoxysilane and γ-methacryloxypropylethoxydimethoxysilane, etc. which trifunctional γ-methacryloxypropylsilane compounds; and trifunctional silane compounds such as γ-methacryloxypropylsilane compounds.
[0052] In formula (II), R is preferably an alkyl group having 1 to 6 carbon atoms, such as methyl, propyl, or normal hexyl, a vinyl group, a phenyl group, or a methacryloxypropyl group, and more preferably an alkyl group or a vinyl group having 1 to 6 carbon atoms. This makes it possible to obtain an organosilicon polymer that satisfies the preferred range of formula (I) above. Furthermore, if Ra is an alkoxy group, this has suitable reactivity in aqueous media and makes it possible to obtain a stable organosilicon polymer, which is preferable, and it is even more preferable that Ra is a methoxy group or an ethoxy group.
[0053] The toner particles preferably have toner base particles, and the toner base particles preferably contain a binder resin. The toner base particles may be used as they are, or a shell containing an organosilicon condensate may be formed on the surface of the toner base particles to use as toner particles. The toner particles may be used as they are, or an external additive such as fine particles may be present on the surface of the toner particles to use as toner.
[0054] The binder resin can be any known resin without any particular limitation. Specific examples include vinyl resins, polyester resins, polyurethane resins, polyamide resins, etc. The binder resin preferably contains a vinyl resin. Polymerizable monomers that can be used in the production of vinyl resins include styrene-based monomers such as styrene and α-methylstyrene; acrylic acid esters such as methyl acrylate and butyl acrylate; methacrylic acid esters such as methyl methacrylate, 2-hydroxyethyl methacrylate, t-butyl methacrylate, and 2-ethylhexyl methacrylate; unsaturated carboxylic acids such as acrylic acid and methacrylic acid; unsaturated dicarboxylic acids such as maleic acid; unsaturated dicarboxylic acid anhydrides such as maleic anhydride; nitrile-based vinyl monomers such as acrylonitrile; halogen-containing vinyl monomers such as vinyl chloride; and nitro-based vinyl monomers such as nitrostyrene.
[0055] The glass transition temperature (Tg) of the binder resin is preferably 40°C or higher and 70°C or lower, and more preferably 40°C or higher and 60°C or lower.
[0056] The toner base particles may contain a colorant. As the colorant, known pigments and dyes of each color of black, yellow, magenta, and cyan, as well as other colors, magnetic materials, and the like can be used without any particular limitation. Black colorants include black pigments such as carbon black. Examples of yellow colorants include yellow pigments and yellow dyes such as monoazo compounds, disazo compounds, condensed azo compounds, isoindolinone compounds, benzimidazolone compounds, anthraquinone compounds, azo metal complexes, methine compounds, and allylamide compounds. Specific examples include CI Pigment Yellow 74, 93, 95, 109, 111, 128, 155, 174, 180, and 185, and CI Solvent Yellow 162.
[0057] Examples of magenta colorants include magenta pigments and magenta dyes such as monoazo compounds, condensed azo compounds, diketopyrrolopyrrole compounds, anthraquinone compounds, quinacridone compounds, basic dye lake compounds, naphthol compounds, benzimidazolone compounds, thioindigo compounds, and perylene compounds. Specifically, CI Pigment Red 2, 3, 5, 6, 7, 23, 48:2, 48: 3, 48:4, 57:1, 81:1, 122, 144, 146, 150, 166, 169, 177, 184, 185, 202, 206, 220, 221, 238, 254, 269, and CI Pigment Violet 19.
[0058] Examples of cyan colorants include cyan pigments and cyan dyes such as copper phthalocyanine compounds and derivatives thereof, anthraquinone compounds, and basic dye lake compounds. Specifically, examples include CI Pigment Blue 1, 7, 15, 15:1, 15:2, 15:3, 15:4, 60, 62, and 66. The content of the colorant is preferably 1.0 part by mass or more and 20.0 parts by mass or less with respect to 100.0 parts by mass of the binder resin or the polymerizable monomer.
[0059] The toner may also contain a magnetic material to make it a magnetic toner. In this case, the magnetic material can also serve as a colorant. Examples of magnetic materials include iron oxides such as magnetite, hematite, and ferrite; metals such as iron, cobalt, and nickel; and alloys of these metals with metals such as aluminum, cobalt, copper, lead, magnesium, tin, zinc, antimony, beryllium, bismuth, cadmium, calcium, manganese, selenium, titanium, tungsten, and vanadium, and mixtures thereof.
[0060] The toner base particles may contain a plasticizer. The plasticizer is not particularly limited, and known plasticizers can be used. Specifically, the esters include esters of monohydric alcohols and aliphatic carboxylic acids, such as behenyl behenate, stearyl stearate, and palmityl palmitate, or esters of monohydric carboxylic acids and aliphatic alcohols; esters of dihydric alcohols and aliphatic carboxylic acids, such as ethylene glycol distearate, dibehenyl sebacate, and hexanediol dibehenate, or esters of dihydric carboxylic acids and aliphatic alcohols; esters of trihydric alcohols and aliphatic carboxylic acids, such as glycerin tribehenate, or esters of trihydric carboxylic acids and aliphatic alcohols; and pentaerythritol tetrastearate. Esters of tetrahydric alcohols and aliphatic carboxylic acids, such as stearate and pentaerythritol tetrapalmitate, or esters of tetrahydric carboxylic acids and aliphatic alcohols; esters of hexahydric alcohols and aliphatic carboxylic acids, such as dipentaerythritol hexastearate and dipentaerythritol hexapalmitate, or esters of hexahydric carboxylic acids and aliphatic alcohols; esters of polyhydric alcohols and aliphatic carboxylic acids, such as polyglycerin behenate, or esters of polyhydric carboxylic acids and aliphatic alcohols; natural ester waxes, such as carnauba wax and rice wax. These may be used alone or in combination. The content of the plasticizer is preferably 1.0 parts by mass or more and 50.0 parts by mass or less, and more preferably 5.0 parts by mass or more and 30.0 parts by mass or less, relative to 100.0 parts by mass of the binder resin or polymerizable monomer.
[0061] The toner base particles may contain a release agent. As the release agent, any known wax may be used without any particular limitation. Specific examples of the release agent include the following. Examples of such waxes include paraffin wax, microcrystalline wax, petroleum waxes and derivatives thereof such as petroleum waxes and derivatives thereof, montan wax and derivatives thereof, hydrocarbon waxes and derivatives thereof produced by the Fischer-Tropsch process, polyolefin waxes and derivatives thereof such as polyethylene, and natural waxes and derivatives thereof such as carnauba wax and candelilla wax. The derivatives include oxides, block copolymers with vinyl monomers, and graft modified products.
[0062] In addition, alcohols such as higher fatty alcohols; fats such as stearic acid and palmitic acid; Examples of the wax include fatty acids or their acid amides, esters, and ketones, hydrogenated castor oil and its derivatives, vegetable waxes, and animal waxes. These may be used alone or in combination. Among these, polyolefins, hydrocarbon waxes produced by the Fischer-Tropsch process, and petroleum-based waxes are preferred because they tend to improve developability and transferability. Incidentally, an antioxidant may be added to these waxes as long as it does not affect the above-mentioned effects.
[0063] The content of the release agent is preferably 1.0 part by mass or more and 30.0 parts by mass or less with respect to 100.0 parts by mass of the binder resin or the polymerizable monomer. The melting point of the release agent is preferably 30°C or higher and 120°C or lower, and more preferably 60°C or higher and 100°C or lower. By using a release agent having the above-mentioned thermal characteristics, the release effect is efficiently exerted and a wider fixing area is ensured.
[0064] The toner base particles may contain a charge control agent. As the charge control agent, any known charge control agent can be used without any particular limitation. Specific examples of the negative charge control agent include metal compounds of aromatic carboxylic acids such as salicylic acid, alkylsalicylic acid, dialkylsalicylic acid, naphthoic acid, and dicarboxylic acids, or polymers or copolymers having metal compounds of the aromatic carboxylic acids; polymers or copolymers having a sulfonic acid group, a sulfonate salt group, or a sulfonate ester group; metal salts or metal complexes of azo dyes or azo pigments; boron compounds, silicon compounds, and calixarenes.
[0065] On the other hand, examples of the positive charge control agent include the following: quaternary ammonium salts, polymeric compounds having quaternary ammonium salts in the side chains, guanidine compounds, nigrosine compounds, imidazole compounds, etc. As the polymer or copolymer having a sulfonate group or a sulfonate ester group, a homopolymer of a sulfonate group-containing vinyl monomer such as styrene sulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid, 2-methacrylamido-2-methylpropanesulfonic acid, vinylsulfonic acid, or methacrylsulfonic acid, or a copolymer of the vinyl monomer shown in the section on binder resin and the above-mentioned sulfonate group-containing vinyl monomer, etc. can be used. The content of the charge control agent is preferably 0.01 parts by mass or more and 5.0 parts by mass or less with respect to 100.0 parts by mass of the binder resin or polymerizable monomer.
[0066] The toner may contain known external additives without any particular limitation. Specific examples include raw silica fine particles such as wet-process silica and dry-process silica, or silica fine particles obtained by subjecting such raw silica fine particles to a surface treatment with a treating agent such as a silane coupling agent, a titanium coupling agent, or silicone oil; and resin fine particles such as vinylidene fluoride fine particles and polytetrafluoroethylene fine particles. The content of the external additive is preferably 0.1 parts by mass or more and 5.0 parts by mass or less with respect to 100.0 parts by mass of the toner particles.
[0067] An example of a method for obtaining the above toner particles will be described below, but the method is not limited to the following. When a shell having an organosilicon polymer is formed on the surface of the toner base particles, the method for forming the shell is not particularly limited, and any known method can be used. Among them, a method in which an organosilicon compound is condensed in an aqueous medium in which the toner base particles are dispersed to form a shell on the toner base particles is preferred, since it is possible to firmly bond the toner base particles and the shell.
[0068] The above method will now be described. When forming a shell on the toner base particles by the above method, it is preferable to include a step (step 1) of obtaining a toner base particle dispersion in which the toner base particles are dispersed in an aqueous medium, and a step (step 2) of mixing an organosilicon compound (and / or a hydrolyzate thereof) with the toner base particle dispersion and causing a condensation reaction of the organosilicon compound in the toner base particle dispersion to form a shell containing an organosilicon polymer on the toner base particles.
[0069] In step 1, the method for obtaining the toner base particle dispersion may include a method of using the dispersion of toner base particles produced in an aqueous medium as is, and a method of putting dried toner base particles into an aqueous medium and dispersing them mechanically. When dispersing dried toner base particles in an aqueous medium, a dispersion aid may be used.
[0070] As the dispersion aid, a known dispersion stabilizer or surfactant can be used. Specific examples of the dispersion stabilizer include the following: inorganic dispersion stabilizers such as tricalcium phosphate, hydroxyapatite, magnesium phosphate, zinc phosphate, aluminum phosphate, calcium carbonate, magnesium carbonate, calcium hydroxide, magnesium hydroxide, aluminum hydroxide, calcium metasilicate, calcium sulfate, barium sulfate, bentonite, silica, and alumina; and organic dispersion stabilizers such as polyvinyl alcohol, gelatin, methyl cellulose, methylhydroxypropyl cellulose, ethyl cellulose, sodium salt of carboxymethyl cellulose, and starch. Examples of the surfactant include anionic surfactants such as alkyl sulfate salts, alkylbenzene sulfonate salts, and fatty acid salts; nonionic surfactants such as polyoxyethylene alkyl ethers and polyoxypropylene alkyl ethers; and cationic surfactants such as alkylamine salts and quaternary ammonium salts. Among these, it is preferable to contain an inorganic dispersion stabilizer, and it is more preferable to contain a dispersion stabilizer containing a phosphate such as tricalcium phosphate, hydroxyapatite, magnesium phosphate, zinc phosphate, or aluminum phosphate.
[0071] In step 2, the organosilicon compound may be added to the toner base particle dispersion liquid as it is, or may be added to the toner base particle dispersion liquid after hydrolysis. Among them, it is preferable to add the organosilicon compound after hydrolysis, since the condensation reaction is easily controlled and the amount of the organosilicon compound remaining in the toner base particle dispersion liquid can be reduced. Hydrolysis is preferably carried out in an aqueous medium with pH adjusted using known acid and base.It is known that the hydrolysis of organosilicon compounds is pH-dependent, and the pH of the hydrolysis is preferably appropriately changed according to the type of organosilicon compound.For example, when methyltriethoxysilane is used as the organosilicon compound, the pH of the aqueous medium is preferably 2.0 or more and 6.0 or less.
[0072] Specific examples of acids for adjusting the pH include inorganic acids such as hydrochloric acid, hydrobromic acid, hydroiodic acid, hypochlorous acid, chlorous acid, chloric acid, perchloric acid, hypobromous acid, bromous acid, bromic acid, perbromic acid, hypoiodous acid, iodous acid, iodic acid, periodic acid, sulfuric acid, nitric acid, phosphoric acid, and boric acid; and organic acids such as acetic acid, citric acid, formic acid, gluconic acid, lactic acid, oxalic acid, and tartaric acid.
[0073] Specific examples of bases for adjusting the pH include alkali metal hydroxides such as potassium hydroxide, sodium hydroxide, and lithium hydroxide, and aqueous solutions thereof; alkali metal carbonates such as potassium carbonate, sodium carbonate, and lithium carbonate, and aqueous solutions thereof; alkali metal sulfates such as potassium sulfate, sodium sulfate, and lithium sulfate, and aqueous solutions thereof; alkali metal phosphates such as potassium phosphate, sodium phosphate, and lithium phosphate, and aqueous solutions thereof; alkaline earth metal hydroxides such as calcium hydroxide and magnesium hydroxide, and aqueous solutions thereof; ammonia; and amines such as triethylamine. do.
[0074] The condensation reaction in step 2 is preferably controlled by adjusting the pH of the toner base particle dispersion. It is known that the condensation reaction of an organosilicon compound is pH-dependent, and the pH at which the condensation reaction is carried out is preferably changed as appropriate depending on the type of organosilicon compound. For example, when methyltriethoxysilane is used as the organosilicon compound, the pH of the aqueous medium is preferably 6.0 or more and 12.0 or less.
[0075] The method for causing the metal compound fine particles A to exist on the surface of the toner particles is not particularly limited, but the following methods can be exemplified. For example, a case where a polyvalent acid metal salt is used as the metal compound fine particles A will be described. (1) A method in which a metal compound serving as a metal source is reacted with a polyvalent acid ion in an aqueous medium in which toner particles are dispersed to obtain a polyvalent acid metal salt. (2) A method in which fine particles of a polyvalent acid metal salt are chemically attached onto the toner particles in an aqueous medium in which the toner particles are dispersed. (3) A method in which fine particles of a polyvalent metal salt are attached onto toner particles by mechanical external force, either in a dry or wet manner.
[0076] Among these, a method of obtaining a polyvalent acid metal salt by reacting a metal compound serving as a metal source with a polyvalent acid ion in an aqueous medium in which toner particles are dispersed is preferred. By using the above method, it becomes possible to uniformly disperse the polyvalent acid metal salt on the surface of the toner particles, which results in efficient formation of a conductive path, and makes it possible to obtain a toner that exhibits injection charging properties using a smaller amount of the polyvalent acid metal salt.
[0077] On the other hand, when the shell contains the metal compound fine particles A, the method for making the metal compound fine particles A exist on the surface of the shell is not particularly limited, but the following methods can be exemplified. For example, a case where a polyvalent acid metal salt is used as the metal compound fine particles A will be described. When the metal compound serving as the metal source is reacted with the polyvalent acid ion in the aqueous medium in which the toner particles are dispersed, an organosilicon compound is added to the aqueous medium at the same time, and a condensation reaction of the organosilicon compound is carried out in the aqueous medium, whereby the shell contains the organosilicon polymer and the metal compound fine particles A, and the metal compound fine particles A are present on the surface of the shell.
[0078] That is, after forming a shell containing an organosilicon polymer on the surface of the toner base particles by the above-mentioned method, it is preferable to simultaneously carry out a reaction between the metal compound and the polyvalent acid ion and condensation of the organosilicon compound in an aqueous medium in which the toner particles having the shell are dispersed. By using the above method, the polyvalent metal salt particles generated in the aqueous medium are fixed to the shell surface by the organosilicon polymer before they grow, so that the dispersibility of the polyvalent metal salt can be improved. In addition, since the polyvalent metal salt is firmly fixed to the shell surface by the organosilicon polymer, a toner with excellent durability can be obtained that can stably exhibit injection charging characteristics even when used for a long period of time. As the metal compound, polyacid and organosilicon compound used in the above method, the above-mentioned metal compound, polyacid and organosilicon compound can be used, respectively.
[0079] The method for producing the toner base particles is not particularly limited, and may be a suspension polymerization method, a solution suspension method, an emulsion aggregation method, a pulverization method, etc. Among these, the suspension polymerization method, the solution suspension method, and the emulsion aggregation method are preferred because they are easy to control the average circularity of the toner within a suitable range. As an example, a method for obtaining toner base particles by suspension polymerization will be described below. First, a polymerizable monomer capable of forming a binder resin and, if necessary, various additives are mixed, and the materials are dissolved or dispersed using a disperser to prepare a polymerizable monomer composition. Various additives include colorants, release agents, plasticizers, charge control agents, polymerization initiators, chain transfer agents, etc. Some examples include: Examples of the dispersing machine include a homogenizer, a ball mill, a colloid mill, and an ultrasonic dispersing machine.
[0080] Next, the polymerizable monomer composition is added to an aqueous medium containing poorly water-soluble inorganic fine particles, and droplets of the polymerizable monomer composition are prepared using a high-speed disperser such as a high-speed stirrer or an ultrasonic disperser (granulation process). Thereafter, the polymerizable monomer in the droplets is polymerized to obtain toner base particles (polymerization step). The polymerization initiator may be mixed when the polymerizable monomer composition is prepared, or may be mixed into the polymerizable monomer composition immediately before forming droplets in the aqueous medium. Alternatively, the compound may be added in a state dissolved in the polymerizable monomer or in another solvent, as required, during or after the granulation of the droplets, that is, immediately before the start of the polymerization reaction.
[0081] After obtaining a binder resin by polymerizing the polymerizable monomer, a solvent removal treatment may be carried out as necessary to obtain a dispersion liquid of toner base particles. When the binder resin is obtained by the emulsion aggregation method or the suspension polymerization method, the polymerizable monomer may be any conventionally known monomer without any particular limitation. Specifically, the vinyl monomers listed in the section on the binder resin may be used.
[0082] As the polymerization initiator, any known polymerization initiator can be used without any particular limitation. Specific examples thereof include the following. Hydrogen peroxide, acetyl peroxide, cumyl peroxide, tert-butyl peroxide, propionyl peroxide, benzoyl peroxide, chlorobenzoyl peroxide, dichlorobenzoyl peroxide, bromomethylbenzoyl peroxide, lauroyl peroxide, ammonium persulfate, sodium persulfate, potassium persulfate, diisopropyl peroxycarbonate, tetralin hydroperoxide, 1-phenyl-2-methylpropyl-1-hydroperoxide, pertriphenylacetic acid-tert-hydroperoxide, tert-butyl performate, tert-butyl peracetate, tert-butyl perbenzoate, tert-butyl perphenylacetate, tert-butyl permethoxyacetate, per-N-(3-tolyl)palmitate-tert-butylbenzoyl peroxide, t-butyl peroxybenzoyl peroxide, Examples of the polymerization initiator include peroxide-based polymerization initiators such as butyl peroxy 2-ethylhexanoate, t-butyl peroxy pivalate, t-butyl peroxy isobutyrate, t-butyl peroxy neodecanoate, methyl ethyl ketone peroxide, diisopropyl peroxycarbonate, cumene hydroperoxide, 2,4-dichlorobenzoyl peroxide, and lauroyl peroxide; and azo- or diazo-based polymerization initiators such as 2,2'-azobis-(2,4-dimethylvaleronitrile), 2,2'-azobisisobutyronitrile, 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis-4-methoxy-2,4-dimethylvaleronitrile, and azobisisobutyronitrile.
[0083] <Toner carrier (developing roller)> 2, the developing roller 23 as a toner carrier has a cylindrical or hollow cylindrical base 23-1 and a conductive elastic layer 23-2. In order to adjust the electrical characteristics, a surface layer 23-3 is provided on the conductive elastic layer 23-2. The surface layer 23-3 may be omitted.
[0084] The base 23-1 is conductive and has a function of supporting the conductive elastic layer provided thereon. Examples of materials include metals such as iron, copper, aluminum, and nickel, and alloys containing these metals such as stainless steel, duralumin, brass, and bronze. The surface of the substrate is plated to provide scratch resistance without impairing electrical conductivity. Furthermore, as the substrate, a substrate made of a resin having a surface coated with a metal to have a conductive surface, or a substrate made of a conductive resin composition can be used.
[0085] The conductive elastic layer 23-2 has a single layer structure or a laminated structure of two or more layers. In particular, in a non-magnetic one-component contact development process, an electrophotographic member having two conductive elastic layers is suitably used as a developing roller. The conductive elastic layer contains elastic materials such as resin and rubber. Specific examples of resin and rubber include the following: polyurethane resin, polyamide, urea resin, polyimide, melamine resin, fluororesin, phenolic resin, alkyd resin, silicone resin, polyester, ethylene-propylene-diene copolymer rubber (EPDM), acrylonitrile-butadiene rubber (NBR), chloroprene rubber (CR), natural rubber (NR), isoprene rubber (IR), styrene-butadiene rubber (SBR), fluororubber, silicone rubber, epichlorohydrin rubber, hydrogenated NBR, and urethane rubber.
[0086] Of these, silicone rubber is preferable. Examples of silicone rubber include polydimethylsiloxane, polymethyltrifluoropropylsiloxane, polymethylvinylsiloxane, polyphenylvinylsiloxane, and copolymers of these siloxanes. These resins and rubbers may be used alone or in combination of two or more, as required.
[0087] In the case of a two-layer conductive elastic layer, it is preferable that the conductive elastic layer has a conductive layer such as a conductive resin layer formed on an elastic layer made of the above-mentioned elastic material. The above-mentioned resin materials can be used for the conductive layer. Among them, polyurethane resin is preferable because it has excellent frictional charging performance with toner, is excellent in flexibility, and therefore has a high contact opportunity with toner, and has abrasion resistance. The materials of the resin and rubber can be identified by measuring the conductive elastic layer with a Fourier transform infrared-visible spectrophotometer.
[0088] Examples of polyurethane resins include ether-based polyurethane resins, ester-based polyurethane resins, acrylic-based polyurethane resins, and carbonate-based polyurethane resins. Among these, polyether polyurethane resins are preferred because they can easily impart a negative charge to the toner through friction with the toner and can easily provide flexibility.
[0089] The polyether polyurethane resin can be obtained by reacting a known polyether polyol with an isocyanate compound. Examples of the polyether polyol include polyethylene glycol, polypropylene glycol, and polytetramethylene glycol. Furthermore, these polyol components may be, if necessary, prepolymerized by chain extension with an isocyanate such as 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), or isophorone diisocyanate (IPDI).
[0090] The isocyanate compound to be reacted with these polyol components is not particularly limited, but examples include the following: aliphatic polyisocyanates such as ethylene diisocyanate, 1,6-hexamethylene diisocyanate (HDI), etc.; alicyclic polyisocyanates such as isophorone diisocyanate (IPDI), cyclohexane 1,3-diisocyanate, cyclohexane 1,4-diisocyanate; aromatic polyisocyanates such as 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate (TDI), diphenylmethane diisocyanate (MDI); and modified products, copolymers, and blocks thereof.
[0091] The conductive elastic layer 23-2 preferably contains a conductive agent to obtain conductivity. Examples of the conductive material include ionic conductive materials and electronic conductive materials such as carbon black. The volume resistivity of the conductive elastic layer is usually 10 3 Ω cm or more 10 11 It is preferable that the resistance is in the range of Ω·cm or less.
[0092] Specific examples of the carbon black include conductive carbon black such as "Ketjen Black" (trade name, manufactured by Lion Corporation) and acetylene black, and carbon black for rubber such as SAF, ISAF, HAF, FEF, GPF, SRF, FT, MT, etc. In addition, carbon black for color inks that has been subjected to an oxidation treatment and pyrolytic carbon black can be used. The amount of carbon black added is preferably 5 parts by mass or more and 50 parts by mass or less per 100 parts by mass of resin or rubber. The content of carbon black in the conductive elastic layer can be measured using a thermogravimetric analyzer (TGA).
[0093] In addition to the above carbon black, the following can be used as conductive agents: graphite such as natural graphite and artificial graphite; metal powders such as copper, nickel, iron and aluminum; metal oxide powders such as titanium oxide, zinc oxide and tin oxide; conductive polymers such as polyaniline, polypyrrole and polyacetylene. These can be used alone or in combination of two or more types as necessary. The conductive elastic layer 23-2 may further contain a charge control agent, a lubricant, a filler, an antioxidant, an anti-aging agent, etc., within the range that does not impair the functions of the above-mentioned resin or rubber and the conductive agent.
[0094] The thickness of the conductive elastic layer 23-2 is preferably 1 μm or more and 5 mm or less, and can be determined by observing and measuring a cross section with an optical microscope. When surface roughness is required when the electrophotographic member is used as a developing roller, fine particles for roughness control can be contained in the conductive elastic layer. The volume average particle diameter of the fine particles for roughness control is preferably 3 μm or more and 20 μm or less. The amount of the fine particles contained in the conductive elastic layer is preferably 1 part by mass or more and 50 parts by mass or less per 100 parts by mass of the resin or rubber. As the roughness control fine particles, fine particles of polyurethane resin, polyester resin, polyether resin, polyamide resin, acrylic resin, polycarbonate resin, or the like can be used.
[0095] The developing roller preferably has a surface layer 23-3 on the conductive elastic layer 23-2 in order to adjust the electrical characteristics. The surface layer is preferably made of an insulating material, and the insulating material is preferably polysiloxane. The polysiloxane can be formed from an alkoxysilane as a raw material by a sol-gel method. Examples of the alkoxysilane that can be used include tetraalkoxysilane, trialkoxysilane, and dialkoxysilane. In particular, it is preferred that the toner carrier has a surface layer having an organosilicon polymer on its outermost surface. The organosilicon polymer may be the organosilicon compound used in the toner described above or the silane compound described below.
[0096] Specific examples of tetraalkoxysilanes include tetramethoxysilane, tetraethoxysilane, tetra(n-propoxy)silane, tetra(iso-propoxy)silane, tetra(n-butoxy)silane, tetra(2-butoxy)silane, and tetra(t-butoxy)silane.
[0097] Trialkoxysilanes include trimethoxyhydrosilane, trimethoxymethylsilane, trimethoxyethylsilane, trimethoxy(n-propyl)silane, and trimethoxy( trimethoxysilanes such as iso-propoxy)silane, trimethoxy(n-butoxy)silane, trimethoxy(2-butoxy)silane, trimethoxy(t-butoxy)silane, trimethoxy(n-hexyl)silane, trimethoxy(n-octyl)silane, trimethoxy(n-decyl)silane, trimethoxy(n-dodeca)silane, trimethoxy(n-tetradeca)silane, trimethoxy(n-pentadeca)silane, trimethoxy(n-hexadeca)silane, trimethoxy(n-octadeca)silane, trimethoxycyclohexylsilane, trimethoxyphenylsilane, and trimethoxy(3-glycidylpropyl)silane; trimethoxysilanes such as triethoxyhydrosilane, triethoxymethylsilane, and triethoxyethyl Examples of triethoxysilanes include silane, triethoxy(n-propyl)silane, triethoxy(iso-propoxy)silane, triethoxy(n-butoxy)silane, triethoxy(2-butoxy)silane, triethoxy(t-butoxy)silane, triethoxy(n-hexyl)silane, triethoxy(n-octyl)silane, triethoxy(n-decyl)silane, triethoxy(n-dodeca)silane, triethoxy(n-tetradeca)silane, triethoxy(n-pentadeca)silane, triethoxy(n-hexadeca)silane, triethoxy(n-octadeca)silane, triethoxycyclohexylsilane, triethoxyphenylsilane, and triethoxy(3-glycidylpropyl)silane.
[0098] Specific examples of dialkoxysilanes include dimethoxysilanes such as dimethoxydimethylsilane, dimethoxydiethylsilane, dimethoxymethylphenylsilane, dimethoxydiphenylsilane, and dimethoxy(bis-3-glycidylpropyl)silane, and diethoxysilanes such as diethoxydimethylsilane, diethoxydiethylsilane, diethoxymethylphenylsilane, diethoxydiphenylsilane, and diethoxy(bis-3-glycidylpropyl)silane.
[0099] The alkoxysilanes can be used alone or in combination. Metal alkoxides can also be added to the alkoxysilane. Examples of metal alkoxides include alkoxides of titanium, zirconium, hafnium, vanadium, niobium, tantalum, tungsten, aluminum, gallium, indium, and germanium. Examples of alkoxides include methoxide, ethoxide, n-propoxide, iso-propoxide, n-butoxide, 2-butoxide, and t-butoxide. The metal alkoxides may have ligands such as acetylacetone and acetoacetate.
[0100] Polysiloxanes and organosilicon polymers can be obtained by first converting the raw material alkoxysilane into a sol, then gelling it after coating. To promote the solization, water, acid, or base can be added as a catalyst. Heating can be performed as necessary. Also, organic solvents can be used to control the coatability and reactivity.
[0101] The organic solvent to be used is not particularly limited as long as it can dissolve the above-mentioned compounds, and examples of the organic solvent include alcohol-based solvents, ether-based solvents, cellosolve-based solvents, ketone-based solvents, ester-based solvents, etc. Specific examples of the alcohol-based solvent include methanol, ethanol, n-propanol, isopropanol, 1-butanol, 2-butanol, t-butanol, 1-pentanol, and cyclohexanol. Specific examples of ether solvents include dimethoxyethane. Specific examples of cellosolve solvents include methyl cellosolve and ethyl cellosolve. Specific examples of ketone solvents include acetone, methyl ethyl ketone, and methyl iso-butyl ketone. Specific examples of ester solvents include methyl acetate and ethyl acetate. Organic solvents can be used alone or in combination of two or more kinds.
[0102] The method for forming the surface layer is not particularly limited, and a commonly used method can be selected. Specifically, examples of the coating method include ring coating, dip coating, spray coating, and coating using a roll coater. After the surface layer is formed, it is possible to carry out a heat treatment in order to dry the solvent. Moreover, by subjecting the surface layer to a surface treatment, it is possible to adjust surface properties such as dynamic friction and surface free energy. Specifically, there is a method of irradiating the surface with active energy rays, and examples of the active energy rays include ultraviolet rays, infrared rays, and electron beams. The thickness of the surface layer is preferably from 0.001 μm to 30 μm, and more preferably from 0.005 μm to 5 μm.
[0103] As the insulating material, an organic resin can be used, specifically, vinyl resin, polyurethane resin, polyamide, urea resin, polyimide, melamine resin, fluororesin, phenol resin, alkyd resin, silicone resin, polyester resin, etc.
[0104] The developing device will be described below with reference to the drawings. However, unless otherwise specified, the dimensions, materials, shapes, relative positions, etc. of the components described below are not intended to limit the scope of the present invention to those alone. Furthermore, unless otherwise specified, the materials, shapes, etc. of the members once described in the following description will be the same as those described at the beginning.
[0105] <Developing device> FIG. 1 shows an example of a schematic cross-sectional view of a process cartridge 10 incorporating a developing device, and will be described below with reference to the same. The developing device 20 includes a developing container 21 having an opening facing the photosensitive drum 11. The developing container 21 includes a developing roller (toner carrier) 23, a peeling roller 24, a regulating blade (toner regulating member) 25, a toner storage section 26, and a toner leakage prevention sheet 27. The developing roller 23 contacts the photosensitive drum 11 and is driven to rotate in the direction of the arrow C in Fig. 3 at a predetermined peripheral speed ratio with respect to the photosensitive drum 11. A predetermined bias is applied to the developing roller 23 from a developing bias power supply 23c, and the electrostatic latent image on the photosensitive drum 11 is developed with toner to be visualized.
[0106] The peeling roller 24 contacts the developing roller 23 and penetrates it by a predetermined amount, and rotates in the same direction (the direction of the arrow D in FIG. 3) as the rotation direction of the developing roller 23. In addition, a bias of the same potential as the bias applied to the developing roller 23 from the developing bias power supply 23c is applied to the peeling roller 24. The peeling roller 24 is composed of a core metal 24a having a diameter of 5 mm, which is a conductive support, and a surface layer 24b made of urethane foam having a thickness of 3 mm. The cells of this urethane foam are open, allowing the toner to enter and exit the urethane, and the diameter of the entire roller including the urethane foam is 13 mm.
[0107] The regulating blade 25 has one end fixed to the developing container 21, and its free end is disposed in contact with the developing roller 23 in the counter direction to the rotational direction of the developing roller 23 (the direction of the arrow C in FIG. 3). The regulating blade 25 applies a charge to the toner, and a predetermined bias is applied from a blade bias power source 25c to regulate the amount of toner on the developing roller 23 to form a thin layer with a uniform toner layer thickness. The regulating blade 25 is composed of a supporting metal plate 25a formed by bending a 1 mm thick SUS plate into an L shape, and a blade 25b made of a 100 μm thick SUS plate joined to the supporting metal plate by laser welding.
[0108] The toner leakage prevention sheet 27 has one end fixed to the developing container 21, and its free end is disposed in contact with the developing roller 23 in the with direction relative to the rotation direction of the developing roller 23 (arrow C in FIG. 3). As the toner leakage prevention sheet 27, a sheet made of PET having a thickness of 50 μm was used.
[0109] In the developing device 20, the toner is sent to the contact portion between the peeling roller 24 and the developing roller 23 by the rotation of the peeling roller 24. The toner sent to the developing roller 23 is sent to the regulating blade 25 as the developing roller 23 rotates. The regulating blade 25 imparts an electric charge to the toner and regulates the amount of toner on the surface of the developing roller 23 to form a uniform toner layer thickness. Here, a developing bias of -300V is applied to the developing roller 23, and a blade bias of -500V is applied to the regulating blade 25. By applying the blade bias, the regulating blade 25 not only regulates the amount of toner to form a thin layer, but also imparts an electric charge to the toner. The toner that has passed the regulating blade 25 is sent to a contact portion with the photosensitive drum 11 as the developing roller 23 rotates, and is used to form an electrostatic latent image formed on the photosensitive drum 11. The toner remaining on the surface of the developing roller 23 after development is transported to a contact section with the peeling roller 24, and is removed (scraped) from the surface of the developing roller 23 by the peeling roller 24. The removed toner is sent to a toner storage section (not shown), and is transported to the peeling roller 24 again.
[0110] Next, various analytical methods will be described in detail below. <Toner Dielectric Constant and Volume Resistivity> The capacitance and conductivity of air and toner are measured by impedance measurement using the parallel plate capacitor method. The equipment used is a toner measurement fixture consisting of a four-terminal sample holder SH2-Z (manufactured by Toyo Corporation) and a torque wrench adapter SH-TRQ-AD (optional), and a material testing system ModuLab XM MTS (manufactured by Solartron Corporation). In addition, a noise-cutting transformer NCT-I3 1.4kVA (manufactured by Denken Seiki Kenkyusho Co., Ltd.) is used to suppress commercial power supply noise, and a shielding box is used to suppress electromagnetic noise. The toner measurement jig uses a four-terminal sample holder and the optional torque wrench adapter SH-TRQ-AD, and uses an upper electrode (Φ25mm solid electrode) SH-H25AU and a lower electrode for liquids / powder (center electrode Φ10mm; guard electrode Φ26mm) SH-2610AU as parallel plate electrodes, and is configured to be able to measure resistances of 0.1Ω to 1TΩ for electrical signals of up to 500Vp-p and DC to 1MHz. In addition, in order to adjust the pressure of the toner sample, a torque wrench adaptor SH-TRQ-AD (manufactured by Toyo Corporation) is attached to a micrometer used for measuring the film thickness between the upper and lower electrodes provided on the four-terminal sample holder. The torque driver used for pressure control is an RTD15CN torque driver (manufactured by Tohnichi Manufacturing Co., Ltd.) with a 6.35 mm square bit, configured to enable the tightening torque to be controlled at 6.5 cN·m.
[0111] The electrical AC characteristics are measured by impedance measurement using a material testing system ModuLab XM MTS (manufactured by Solartron Corporation). The ModuLab XM MTS consists of a control module XM MAT 1MHz, a high voltage module XM MHV100, a femto current module XM MFA, and a frequency response analysis module XM MRA 1MHz, and the control software uses the company's XM-studio MTS Ver.3.4. The toner measurement conditions are Normal Mode, in which only measurement is performed, with an AC level of 7 Vrms, a DC bias of 0 V, and a sweep frequency of 1 MHz to 0.01 Hz (12 points / decade or 6 points / decade). In addition, in order to suppress noise and shorten measurement time, the following settings are added for each sweep frequency. Sweep frequency: 1MHz to 10Hz Measurement integration time: 64 cycles Sweep frequency 10Hz~1Hz Measurement integration time 24 cycles Sweep frequency 1Hz~0.01Hz Measurement integration time 1 cycle Under the above measurement conditions, the impedance characteristics, which are electrical AC characteristics, are measured.
[0112] By performing measurements under the above conditions, a toner measurement jig based on the parallel plate capacitor method is used, and the impedance characteristics of the air and sample at the film thickness d according to the pressure torque and the measurement electrode S of Φ10 mm are obtained. From the obtained impedance characteristics of the air and the sample, data correction processing of the measurement system is performed to obtain highly reliable capacitance C and conductance (conductivity) G. From the obtained capacitance C, conductance (conductivity) G, and the geometric shape of the toner measurement jig (parallel plate electrode size S and sample film thickness), the relative dielectric constant and conductivity, which are electrical properties, are obtained.
[0113] When using the SH2-Z 4-terminal sample holder for the first time, two verifications must be carried out to find the optimal measurement conditions, since there are individual differences in the SH2-Z 4-terminal sample holders used in powder measurement fixtures. The first verification is the film thickness dependency characteristic of the four-terminal sample holder. The dependency on air thickness (distance between the upper and lower electrodes) is measured, the error between the theoretical value of capacitance and the measured value is confirmed, and the optimal range or film thickness that minimizes the measurement error is identified. The second verification is the measurement of mechanical error. When measuring toner samples, a torque-controlled load is applied to keep the volume density constant. In contrast, no load is applied when measuring air. At this time, film thickness errors occur due to the influence of dimensions such as mechanical processing accuracy. Therefore, the offset value between the loaded and unloaded states of the tightening torque control value (6.5 cN m for this jig) is confirmed and used as the offset correction value.
[0114] Specific sample preparation and measurement procedures are as follows. (1) Toner is piled up on the central electrode part of the lower electrode, and formed into a trapezoidal shape with a height of 5 mm. (2) The lower electrode with the toner piled up is attached to the four-terminal sample holder SH2-Z, and the upper electrode is lowered. (3) At this time, the upper electrode is lowered to the upper end of the toner while keeping it constant so as not to rotate inadvertently. (4) While rotating the upper electrode left and right, a smoothing process is performed so that the toner becomes smooth. (5) Using a micrometer, adjust the film thickness to a desired value while keeping the rotation direction of the upper electrode constant. (6) Apply pressure using a torque driver with the tightening torque controlled at 6.5 cN m. (7) Measure the sample thickness using a micrometer. (8) Impedance measurement is performed under the above conditions. (9) After the measurement is completed, raise the upper electrode and remove the lower electrode. At this time, remove the lower electrode while being careful not to let toner get into the contact terminal for the lower electrode of the four-terminal sample holder, and protect it with masking tape. (10) Clean the upper and lower electrodes. (11) Remove the masking tape and attach the lower electrode. (12) The thickness of the sample film d obtained in step (7) is adjusted to be equal to the thickness of air t, taking into account the offset correction in the no-load state, and the rotation direction of the upper electrode is kept constant. (13) Conduct air impedance measurements. (14) If the measurement data (dielectric tangent; tan δ) of the air measured in step (13) is 0.002 or more in the frequency range of 100 Hz to 0.01 Hz, cleaning is insufficient, so the work is repeated from the cleaning process in step (10). The measurements are carried out at 25°C.
[0115] The specific data processing procedure is as follows. (15) From the measured impedance characteristics of the air, the error of the phase characteristics relative to the theoretical value is calculated, and phase correction data for the material testing system ModuLab XM MTS (manufactured by Solartron) is obtained. (16) The phase correction data calculated in step (15) is applied to the air impedance characteristic measured in step (13) to obtain a phase-corrected air impedance characteristic. (17) The electrostatic capacitance Ca is calculated from the admittance Ya=Ga+jωCa of the phase-corrected impedance characteristic of air, and the error from the theoretical value is calculated to obtain correction data α for the film thickness error. (18) The phase correction process obtained in step (15) is applied to the impedance characteristics of the toner sample measured in step (8). (19) By calculating the complex admittance Ym = Gm + jωCm of the characteristics that have been subjected to the phase correction processing in step (18) using the capacitance Ca of the air obtained in step (17) and the correction data α thereof, highly reliable relative dielectric constant and conductivity of the toner sample can be obtained.
[0116] The specific procedure for identifying the electrical properties is as follows. The electrical property parameters of the dielectric constant and volume resistivity of the toner sample obtained in step (19) are identified by carrying out the following procedure. (20) Identify the relative dielectric constant at the frequency at which the dielectric tangent tan δ is at its minimum in the frequency range of 1 kHz to 400 kHz. (21) The electrical conductivity at a frequency of 0.01 Hz is determined, and the inverse of the electrical conductivity is identified as the volume resistivity. In addition, in the case of an ohmic characteristic, the inverse of the electrical conductivity at an arbitrary low frequency may be identified as the volume resistivity. From the above measurement results, the capacitance per unit area of the toner, Ctn (pF / cm), calculated using a parallel plate capacitor model with a thickness 1.5 times the toner particle diameter (weight average particle diameter D4), is calculated using the following formula: 2 ) and volume resistivity per unit area Rtn (Ω / cm 2 ) is calculated. Ctn = (dielectric constant of vacuum) x (measured relative dielectric constant) x (unit area) / (thickness) Rtn = (thickness) / (unit area) / (measured conductivity)
[0117] <Measurement of electrostatic capacitance and volume resistance of toner carrier> Impedance measurements are used to measure the electrical AC characteristics of the toner carrier: capacitance Cdr and volume resistance Rdr. To evaluate the electrical properties of toner carriers, a material testing system ModuLab XM MTS (Solatron) is usually used, and in the case of high resistance materials that exhibit insulating properties, a high voltage impedance measurement system (Toyo Corporation) is also used. In evaluating the electrical properties of toner carriers, there is concern about the influence of edge capacitors (stray capacitance) that occur at the ends where the measurement electrodes come into contact with the toner carrier surface, so a measurement jig with a cylindrical microelectrode was devised and used. Specifically, a Φ0.65 mm cylindrical check terminal CH2-3 (manufactured by Mac Eight) was soldered to an SHV connector 317.580.000 (manufactured by RADIALL) having an insulation resistance of 1 TΩ, and a contact electrode jig for passing electricity through the toner carrier was fabricated and used. A probe used in a manual prober was used as a contact jig that contacts the core metal of the toner carrier. The probe consisted of a positioner HP80 / RM-GB type for position control, a high-voltage probe HCP40-HV1.5K type, and a needle-shaped probe with a tip radius of 25 μm. The probe is made up of a PT250-25 (Hisol Corporation). The stray capacitance of the measurement jig using these probes is 0.1 pF or less.
[0118] The electrical AC characteristics are measured by impedance measurement using a material testing system ModuLab XM MTS (manufactured by Solartron Corporation). The ModuLab XM MTS consists of a control module XM MAT 1MHz, a high voltage module XM MHV100, a femto current module XM MFA, and a frequency response analysis module XM MRA 1MHz, and the control software uses the company's XM-studio MTS Ver.3.4. The measurement conditions for the toner carrier are Normal Mode, in which only measurement is performed, with an AC level of 7 Vrms, a DC bias of 0 V, and a sweep frequency of 1 MHz to 0.01 Hz (12 points / decade or 6 points / decade). In addition, in consideration of noise suppression and shortening of measurement time, the following settings are added for each sweep frequency: Sweep frequency 1MHz~10Hz Measurement integration time 128 cycles Sweep frequency 10Hz~1Hz Measurement integration time 64 cycles Sweep frequency 1Hz~0.1Hz Measurement integration time 24 cycles Sweep frequency 0.1Hz~0.01Hz Measurement integration time 1 cycle Under the above measurement conditions, the impedance characteristics, which are electrical AC characteristics, are measured.
[0119] When measuring a toner carrier, which is a high resistance body exhibiting insulating properties, impedance measurement is performed using a high voltage impedance system (manufactured by Toyo Corporation). The high-voltage impedance measurement system is composed of the Dielectric Impedance Measurement System 126096W, which consists of the Impedance Analyzer 1260 and the Dielectric Interface 1296, as well as the High Voltage Amplifier 2220 (Trek) as a DC amplifier, the High Speed Amplifier HVA800 (Toyo Corporation) as an AC amplifier, the High Voltage AC / DC Interface 6792 (Toyo Corporation) for high voltage control of AC / DC signals, and the Reference Box 6796 (Toyo Corporation) for monitoring the high voltage signal and performing capacitance correction. The control software used is SMaRT Ver3.31. The measurement conditions for the toner carrier are External Mode, which performs correction processing using an external capacitance, AC level 7Vrms, DC bias 0V, and sweep frequency 100kHz to 0.0215Hz (12 points / decade or 6 points / decade).
[0120] In addition, taking into consideration the reproducibility and accuracy of the measurement data and the measurement time, the following settings are added for each sweep frequency. Sweep frequency 100kHz 10kHz Measurement delay cycle 1000 Measurement integration time 768 cycles Sweep frequency 10kHz~1kHz Measurement delay cycle 500 Measurement integration time 512 cycles Sweep frequency 1kHz~100Hz Measurement delay cycle 20 Measurement integration time 384 cycles Sweep frequency 100Hz~10Hz Measurement delay cycle 10 Measurement integration time 64 cycles Sweep frequency 10Hz~1Hz Measurement delay cycle 1 Measurement integration time 16 cycles Sweep frequency 1Hz~0.1Hz Measurement delay cycle 1 Measurement integration time 8 cycles Sweep frequency 0.1Hz~0.0215Hz Measurement delay cycle 1 Measurement integration time 4 cycles Under the above measurement conditions, the impedance characteristics, which are electrical AC characteristics, are measured.
[0121] In addition, in the impedance measurement, a noise cut transformer NCT-I3 1.4kVA (manufactured by Denken Seiki Kenkyusho Co., Ltd.) is used as a means for suppressing noise from the commercial power supply, and a shield box is used as a means for suppressing electromagnetic noise. The specific measurement procedure is as follows. (1) Place only the toner carrier in the Teflon V-groove receiver. (2) Using a needle-shaped probe as a contact jig, electrical continuity is established with the core metal of the toner carrier. (3) The cylindrical electrode for measurement is fixed in a position where there is no effect of stray capacitance, and data is measured in the open state. If the capacitance is 0.1 pF or more at this time, the measurement is not correct. Also, there is some problem with the measurement jig or measurement device, and it needs to be improved. (4) A cylindrical electrode with a diameter of 0.65 mm is placed in contact with the toner carrier and measurements are performed. (5) If ohmic characteristics are observed during measurement, it is not necessary to measure down to low frequencies (0.01 Hz).
[0122] The specific data processing procedure is as follows. Phase correction processing is performed only on the measurement results obtained by the material testing system ModuLab. From the measurement data (phase characteristics) in the open state in step (3), the error from the theoretical value is calculated as correction data. The measurement data from step (4) is subjected to a phase correction process using the phase correction data. (6) The complex admittance Ym = Gm + jωCm of the impedance characteristic that has been measured or has been subjected to phase correction processing is converted into the characteristic per unit area of 1 square centimeter from the measurement electrode area of Φ0.65 mm.
[0123] The specific identification procedure is as follows. <Method for identifying the number of elementary processes> The presence or absence of a maximum value is identified by the zero-crossing detection method, which is the first derivative of the frequency dependence of the dielectric tangent tanδ. If no maximum value is found, an interface with different dielectric relaxations has not been formed, and the elementary process is determined to be 1. If one maximum value is found, it can be determined that an interface with different dielectric relaxations has been formed, and the elementary process is determined to be 2.
[0124] <Resistance value identification method> At this time, on the high frequency side of 0.1 Hz or more, different identification procedures are carried out for cases where the dielectric tangent tan δ is 10 or more and cases where it is not. The case where the dielectric tangent tan δ is 10 or more will be described below. Create a log-log graph with conductance (conductivity) Gm on the vertical axis and capacitance Cm on the horizontal axis. Determine the measurement frequency range where the first derivative of the Gm-Cm characteristic is -0.5 or less, and find the median of conductance (conductivity) Gm in this frequency range. Identify the reciprocal of the found median as the resistance value. Below, the case where the dielectric tangent tan δ is not 10 or more will be described. The frequency at which the dielectric tangent tanδ shows a maximum value is determined by the zero-cross detection method, which is the first derivative of the frequency dependence of the dielectric tangent tanδ. The reciprocal of the conductance (conductivity) Gm at the determined frequency is identified as the resistance value. Also, if no maximum value of the dielectric tangent tanδ is detected, the reciprocal of the conductance (conductivity) Gm at 0.01 Hz is identified as the resistance value. From the obtained resistance value, the volume resistance value Rdr per unit area of the toner carrier is calculated by area conversion.
[0125] <Method for identifying capacitance> To identify the capacitance, a complex response function called modulus is used. The modulus is defined as M=jωZ and can be calculated from the impedance characteristic Z (the reciprocal of admittance Y). Calculate the frequency dependence of the imaginary term of the modulus M, and find the frequency at which it has a maximum value. The frequency at which the maximum value is shown can be identified by a zero-cross detection method using a first-order differential calculation, and the capacitance Cm at that frequency is identified as a parameter. The following describes the case where multiple maximum values exist. A double logarithmic graph is created with the conductance (conductivity) Gm on the vertical axis and the capacitance Cm on the horizontal axis, and the first derivative of the Gm-Cm characteristic is calculated to determine the range of measurement frequencies where the first derivative is -1. At this time, the frequency showing the multiple maximum values is selected to be the maximum value closest to the measurement frequency where the first derivative is -1. Furthermore, if the frequency showing multiple maximum values has the same difference as the measurement frequency at which the first differential calculation is -1, the frequency on the higher frequency side is selected. Thus, the capacitance Cm at the frequency showing the obtained maximum value is identified. From the obtained capacitance Cm, the capacitance Ctn per unit area of the toner carrier is calculated by area conversion.
[0126] <Method of measuring weight average particle size (D4) and number average particle size (D1)> The weight average particle diameter (D4) and the number average particle diameter (D1) of the toner, toner particles, or toner base particles (hereinafter, also referred to as toner, etc.) are calculated as follows. The measuring device used is a precision particle size distribution measuring device using the narrow hole electrical resistance method, "Coulter Counter Multisizer 3" (registered trademark, manufactured by Beckman Coulter, Inc.), equipped with a 100 μm aperture tube. The measurement conditions and data analysis were performed using the dedicated software "Beckman Coulter The system used was "Multisizer 3 Version 3.51" (Beckman Coulter, Inc.). The measurement was performed with an effective measurement channel count of 25,000 channels. The electrolyte solution used for the measurement is prepared by dissolving special grade sodium chloride in ion-exchanged water to a concentration of 1.0%, for example, "ISOTON II" (manufactured by Beckman Coulter, Inc.). Before performing measurements and analysis, the dedicated software is set up as follows. In the "Change standard measurement method (SOMME)" screen of the dedicated software, set the total count number in the control mode to 50,000 particles, the number of measurements to 1, and the Kd value to the value obtained using "Standard particle 10.0 μm" (Beckman Coulter, Inc.). Press the "Threshold / Noise level measurement button" to automatically set the threshold and noise level. In addition, set the current to 1,600 μA, the gain to 2, the electrolyte to ISOTON II, and check "Flush aperture tube after measurement." In the "Pulse to particle size conversion setting" screen of the dedicated software, set the bin interval to logarithmic particle size, the particle size bin to 256 particle size bins, and the particle size range to 2 μm to 60 μm.
[0127] The specific measurement method is as follows. (1) Pour 200.0 mL of the electrolyte solution into a 250 mL round-bottom glass beaker made exclusively for the Multisizer 3, set it on the sample stand, and stir the stirrer rod counterclockwise at 24 revolutions per second. Then, use the "Aperture tube flush" function of the dedicated software to remove dirt and air bubbles from inside the aperture tube. (2) Place 30.0 mL of the electrolytic aqueous solution into a 100 mL glass flat-bottom beaker. Add 0.3 mL of a dilution obtained by diluting "Contaminon N" (a neutral detergent for precision measuring instruments with a pH of 7, consisting of a nonionic surfactant, an anionic surfactant, and an organic builder, 10% aqueous solution manufactured by Wako Pure Chemical Industries, Ltd.) three times by mass with ion-exchanged water as a dispersant. (3) Prepare an ultrasonic disperser "Ultrasonic Dispersion System Tetra150" (manufactured by Nikkaki Bios Co., Ltd.) with an electrical output of 120 W, which incorporates two oscillators with an oscillation frequency of 50 kHz and a 180-degree phase shift. Place 3.3 L of ion-exchanged water into the water tank of the ultrasonic disperser, and add 2.0 mL of Contaminon N to this water tank. (4) Set the beaker in (2) above into the beaker fixing hole of the ultrasonic disperser, and operate the ultrasonic disperser. Then, adjust the height position of the beaker so that the resonance state of the liquid level of the electrolytic aqueous solution in the beaker is maximized. (5) While irradiating the electrolytic aqueous solution in the beaker in (4) above with ultrasonic waves, add 10 mg of toner or the like little by little to the electrolytic aqueous solution and disperse it. Then, continue the ultrasonic dispersion treatment for another 60 seconds. Note that during ultrasonic dispersion, appropriately adjust the water temperature in the water tank so that it is 10°C or higher and 40°C or lower. (6) Using a pipette, drop the electrolytic aqueous solution in (5) above in which toner or the like is dispersed into the round-bottom beaker in (1) above installed in the sample stand, and adjust it so that the measured concentration becomes 5%. Then, perform the measurement until the number of measured particles reaches 50,000. (7) Analyze the measurement data using the dedicated software attached to the device, and calculate the weight average particle size (D4) and the number average particle size (D1). Note that when set to graph / volume% in the dedicated software, the "average diameter" on the "Analysis / Volume Statistical Value (Arithmetic Mean)" screen is the weight average particle size (D4). When set to graph / number% in the dedicated software, the "average diameter" on the "Analysis / Number Statistical Value (Arithmetic Mean)" screen is the number average particle size (D1).
[0128] <Observation of the Toner Surface by STEM-EDS> Using a scanning transmission electron microscope (STEM), a section including the outermost surface of the toner is observed by the following method. First, the toner is sufficiently dispersed in a room temperature curable epoxy resin and then cured in an atmosphere at 40°C for 2 days. From the obtained cured product, a thin sample with a thickness of 50 nm including the outermost surface of the toner is cut out using a microtome equipped with a diamond blade (EM UC7: manufactured by Leica). This sample is magnified 100,000 times using STEM (JEM2800 type: manufactured by JEOL Ltd.) under the conditions of an acceleration voltage of 200 V and an electron beam probe size of 1 mm, and the outermost surface of the toner is observed. Subsequently, the constituent elements of the obtained outermost surface of the toner are analyzed using energy dispersive X-ray spectroscopy (EDS), and an EDS mapping image (256×256 pixels (2.2 nm / pixel), integration times 200 times) is created. In the created EDS mapping image, when a signal derived from a metal element is observed on the surface of the toner and particles are observed at the same position in the STEM image, the particles are defined as metal compound fine particles A.
[0129] <Method for Confirming a Shell Containing an Organosilicon Polymer by STEM-EDS> Using a scanning transmission electron microscope (STEM), a cross-section of the toner is observed by the following method. First, the toner is sufficiently dispersed in a room temperature curable epoxy resin and then cured in an atmosphere at 40°C for 2 days. From the obtained cured product, a thin sample with a thickness of 50 nm is cut out using a microtome equipped with a diamond blade (EM UC7: manufactured by Leica). This sample is magnified 100,000 times using STEM (JEM2800 type: manufactured by JEOL Ltd.) under the conditions of an acceleration voltage of 200 V and an electron beam probe size of 1 mm, and the cross-section of the toner is observed. At this time, according to the method for measuring the number average particle diameter (D1) of the toner described later, a cross-section of a toner having a maximum diameter of 0.9 times to 1.1 times the number average particle diameter (D1) when measuring the same toner is selected. Subsequently, the constituent elements of the cross-section of the obtained toner are analyzed using energy-dispersive X-ray spectroscopy (EDS), and an EDS mapping image (256×256 pixels (2.2 nm / pixel), integration times: 200 times) is created. In the created EDS mapping image, a signal derived from the constituent elements of the organosilicon polymer is confirmed on the contour of the cross-section of the toner particles. The signal is observed over 80% or more of the length of the contour of the cross-section of the toner particles, and by the <Method for Confirming Organosilicon Polymer> described below When it is confirmed that the above signal is derived from the organosilicon polymer, the above signal is used as an image of a shell containing the organosilicon polymer.
[0130] <Method for Confirming Organosilicon Polymer> The organosilicon polymer on the surface of the toner particles is confirmed by comparing the ratio (Si / O ratio) of the elemental contents (atomic%) of Si and O with a standard sample. For the standard samples of the organosilicon polymer and the silica fine particles respectively, EDS analysis is performed under the conditions described in the <Method for Confirming the Shell Containing Organosilicon Polymer by STEM-EDS> to obtain the elemental contents (atomic%) of Si and O respectively. Let the Si / O ratio of the organosilicon polymer be A, and the Si / O ratio of the silica fine particles be B. Select the measurement conditions under which A becomes significantly larger than B. Specifically, for the standard sample, 10 measurements are performed under the same conditions to obtain the additive average values of A and B respectively. Select the measurement conditions under which the obtained average value satisfies A / B > 1.1. In the EDS image, if the Si / O ratio of the portion where silicon is detected is on the A side rather than [(A + B) / 2], the portion is determined to be an organosilicon polymer. On the other hand, if the Si / O ratio is on the B side rather than [(A + B) / 2], the portion is determined to be silica. As the standard sample of the organosilicon polymer particles, Tospearl 120A (Momentive Performance Materials Japan G.K.) is used, and as the standard sample of the silica fine particles, HDK V15 (Asahi Kasei) is used.
[0131] <Method for Detecting Polyvalent Metal Salt> Using time-of-flight secondary ion mass spectrometry (TOF-SIMS), the polyvalent acid metal salt on the surface of the toner particles is detected by the following method. The toner sample is analyzed using a TOF-SIMS (TRIFTIV: manufactured by ULVAC-PHI, Inc.) under the following conditions. Primary ion species: Gold ions (Au + ) Primary ion current: 2pA ·Analysis area: 300×300μm 2 Resolution: 256×256 ·Analysis time: 3min Repetition rate: 8.2kHz Charge neutralization: ON Secondary ion polarity: Positive Secondary ion mass range: m / z 0.5~1850 Sample substrate: Indium The analysis was performed under the above conditions, and secondary ions including metal ions and polyvalent acid ions (e.g., TiPO in the case of titanium phosphate) were detected. 3 (m / z 127), TiP 2 O 5 When a peak derived from (m / z 207) or the like) is detected, a polyvalent acid metal salt is present on the toner particle surface. EXAMPLES
[0132] The present invention will be specifically described with reference to the following Production Examples and Examples. However, these do not limit the present invention in any way. In the Production Examples and Examples, "parts" and "%" are all by mass unless otherwise specified.
[0133] <Toner manufacturing example> <Example of manufacturing organosilicon compound liquid> 70.0 parts of ion-exchanged water Methyltriethoxysilane 30.0 parts The above materials were weighed into a 200 mL beaker, and the pH was adjusted to 3.5 with 10% hydrochloric acid. After that, the mixture was heated to 60° C. in a water bath while stirring for 1.0 hour to obtain an organosilicon compound liquid. Got it.
[0134] <Examples of manufacturing aqueous media> <Aqueous medium 1> 11.2 parts of sodium phosphate (12-hydrate) was added to a reaction vessel containing 390.0 parts of ion-exchanged water, and the mixture was kept at 65°C for 1.0 hours while purging with nitrogen. The mixture was stirred at 12000 rpm using a TK homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.). While maintaining the stirring, an aqueous calcium chloride solution in which 7.4 parts of calcium chloride (2-hydrate) was dissolved in 10.0 parts of ion-exchanged water was added to the reaction vessel all at once to prepare an aqueous medium containing a dispersion stabilizer. Furthermore, 1.0 mol / L of hydrochloric acid was added to the aqueous medium in the reaction vessel to adjust the pH to 6.0, and aqueous medium 1 was obtained.
[0135] <Aqueous medium 2~6> Aqueous media 2 to 6 were obtained in the same manner as in the production example of aqueous medium 1, except that the amounts of each material added were changed to the amounts shown in Table 1 below.
[0136] [Table 1]
[0137] <Production of untreated magnetic material> An aqueous solution containing ferrous hydroxide was prepared by mixing 1.0 equivalent of caustic soda solution relative to iron element and 1.5 mass% sodium silicate calculated as silicon element relative to iron element into an aqueous solution of ferrous sulfate. While maintaining the pH of the aqueous solution at 9.0, air was blown in and an oxidation reaction was carried out at 80°C to 90°C to prepare a slurry liquid for generating seed crystals. Next, an aqueous solution of ferrous sulfate was added to this slurry so that the amount of alkali (sodium content of caustic soda) was 1.0 equivalent. The pH of the slurry was then maintained at 8.0, and the oxidation reaction was carried out while blowing in air, to obtain a slurry containing magnetic iron oxide. This slurry was filtered and washed, and then filtered again. It was then crushed and dried to obtain untreated magnetic material.
[0138] <Preparation of silane compound> 20 parts of isobutyltrimethoxysilane was added dropwise to 80 parts of ion-exchanged water while stirring. Then, this aqueous solution was kept at pH 5.5 and temperature 40°C, and dispersed for 2 hours at 0.46 m / s using a dispersing blade to carry out hydrolysis, thereby obtaining a silane compound, which is an aqueous solution containing a hydrolyzate.
[0139] <Production of treated magnetic material> The untreated magnetic material was placed in a Henschel mixer (manufactured by Nippon Coke & Engineering Co., Ltd.) and the silane compound was added by spraying while dispersing at 34.5 m / s. After dispersing for 10 minutes, the magnetic material with the silane compound adsorbed thereon was taken out and left to stand at 160°C for 2 hours to dry the treated magnetic material and to allow the condensation reaction of the silane compound to proceed. The magnetic material was then passed through a sieve with 100 μm openings to obtain the treated magnetic material.
[0140] <Preparation of polymerizable monomer composition> <Polymerizable monomer composition 1> Styrene 60.0 parts CI Pigment Red 122 8.0 parts The above materials were placed in an attritor (manufactured by Nippon Coke and Engineering Co., Ltd.) and further dispersed using zirconia particles having a diameter of 1.7 mm at 220 rpm for 5.0 hours, after which the zirconia particles were removed to prepare a colorant dispersion in which the pigment was dispersed. The following materials were then added to the colorant dispersion: Styrene 15.0 parts ・25.0 parts n-butyl acrylate Hexanediol diacrylate 0.5 parts Polyester resin 5.0 parts (A condensation polymer of terephthalic acid and 2 moles of propylene oxide adduct of bisphenol A, with a weight average molecular weight Mw of 10,000 and an acid value of 8.2 mgKOH / g) Release agent (hydrocarbon wax, melting point: 79°C) 9.0 parts The above materials were kept at 65° C. and uniformly dissolved and dispersed at 500 rpm using a TK homomixer to prepare a polymerizable monomer composition 1.
[0141] <Polymerizable monomer composition 2> Styrene: 75.0 parts n-Butyl acrylate: 25.0 parts Hexanediol diacrylate: 0.5 parts Treated magnetic material: 90.0 parts by weight Polyester resin: 5.0 parts (A condensation polymer of terephthalic acid and 2 moles of propylene oxide adduct of bisphenol A, with a weight average molecular weight Mw of 10,000 and an acid value of 8.2 mgKOH / g) Release agent (hydrocarbon wax, melting point: 79°C): 15.0 parts The above materials were kept at 65° C. and uniformly dissolved and dispersed at 500 rpm using a TK homomixer to prepare a polymerizable monomer composition 2.
[0142] <Production Example of Toner Base Particle Dispersion> <Toner base particle dispersion 1> (granulation process) While maintaining the temperature of the aqueous medium 1 at 70° C. and the rotation speed of the stirring device at 12,500 rpm, the polymerizable monomer composition 1 was charged into the aqueous medium 1, and 8.0 parts of t-butyl peroxypivalate as a polymerization initiator was added. Granulation was continued for 10 minutes while maintaining the stirring device at 12,500 rpm. (Polymerization process) The high-speed agitator was changed to an agitator equipped with a propeller agitator, and polymerization was carried out for 5.0 hours while stirring at 200 rpm, maintaining the temperature at 70°C, and then heating to 85°C for 2.0 hours to carry out the polymerization reaction. The temperature was then raised to 98°C and heated for 3.0 hours to remove residual monomers. Thereafter, the temperature was lowered to 55°C, and the temperature was maintained at 55°C for 5.0 hours while continuing to stir. The temperature was then lowered to 25°C. Ion-exchanged water was added to adjust the toner base particle concentration in the dispersion to 30.0%, and toner base particle dispersion 1 in which toner base particles 1 were dispersed was obtained. The weight average particle diameter (D4) of toner base particles 1 was 6.7 μm.
[0143] <Toner base particle dispersion liquid 2-7> In the manufacturing example of the toner base particle dispersion 1, the combination of the aqueous medium and the polymerizable monomer composition was Toner base particle dispersions 2 to 7 were obtained in the same manner as in the production example of toner base particle dispersion 1, except for changing the ingredients as shown in Table 2. The weight average particle size (D4) of the obtained toner base particles is shown in Table 2.
[0144] [Table 2]
[0145] <Toner particle manufacturing example> <Toner particle 1> The toner base particle dispersion 1 was adjusted to pH 1.5 by adding 1 mol / L hydrochloric acid and stirred for 1.0 hour, and then washed with ion-exchanged water, filtered and dried to obtain toner particles 1. The weight average particle size (D4) of the toner particles 1 was 6.7 μm.
[0146] <Toner particles 2 to 7> Toner particles 2 to 7 were obtained in the same manner as in the production example of toner particle 1, except that in the production example of toner particle 1, the toner base particle dispersion liquid was changed to that shown in Table 3. The weight average particle size (D4) of the obtained toner particles is shown in Table 3.
[0147] [Table 3]
[0148] <Toner Particle 1A> (Organosilicon Polymer Formation Process) The following samples were weighed and placed in a reaction vessel, and mixed using a propeller agitator. Toner base particle dispersion 1 500.0 parts Organosilicon compound liquid 40.0 parts Next, the pH of the resulting mixture was adjusted to 9.5 using a 1 mol / L NaOH aqueous solution, and the temperature of the mixture was increased to 50° C., after which it was held for 1.0 hour while being mixed using a propeller stirring blade.
[0149] (Polyvalent acid metal salt attachment process) Titanium lactate 44% aqueous solution (TC-310: Matsumoto Fine Chemical Co., Ltd.) 3.2 parts (equivalent to 1.4 parts of titanium lactate) Organosilicon compound liquid 10.0 parts Next, the above sample was weighed and mixed in a reaction vessel, and then 1 mol / L NaOH water was added. The pH of the resulting mixture was adjusted to 9.5 using a solution, and was maintained for 4.0 hours. After lowering the temperature to 25° C., the pH was adjusted to 1.5 with 1 mol / L hydrochloric acid, and the mixture was stirred for 1.0 hour, and then filtered while being washed with ion-exchanged water to obtain toner particles 1A.
[0150] <Toner particles 2A, 3A, 1B> Toner particles 2A, 3A and 1B were obtained in the same manner as in the production example of toner particle 1A, except that the amounts of the toner base particle dispersion, the organosilicon compound liquid and the 44% aqueous titanium lactate solution were changed to those shown in Table 4.
[0151] [Table 4]
[0152] <Toner manufacturing example> <Toner 1> Toner particles 1A were used as toner 1. When the cross section of Toner 1 was observed by STEM-EDS, a shell containing an organosilicon polymer and fine particles of a polyvalent metal salt were observed on the surface of the toner particles. In addition, when Toner 1 was analyzed by time-of-flight secondary ion mass spectrometry (TOF-SIMS), ions derived from a titanium phosphate compound were detected. The titanium phosphate compound is a reaction product of titanium lactate and phosphate ions derived from sodium phosphate or calcium phosphate in the toner base particle dispersion liquid 1. The volume resistivity of toner 1 is 2.9×10 13 (Ω·cm), the relative dielectric constant was 1.9, and the weight average particle size (D4) was 6.7 μm. The physical properties of Toner 1 are shown in Table 6.
[0153] <Toner 4, 6, 13> The toner particles 2A were used as toner 4, the toner particles 3A were used as toner 6, and the toner particles 1B were used as toner 13. The physical properties of toners 4, 6 and 13 are shown in Table 6.
[0154] <Toner 2> ·Toner particles 1 100.0 parts ·Silica fine particles 1 2.0 parts The above materials were charged into a SUPERMIXER PICCOLO SMP-2 (manufactured by Kawata Corporation), and mixed at 3000 rpm for 5 minutes while heating the inside of the tank to 45°C by charging 45°C hot water into the jacket. ·Silica fine particles 2 2.0 parts ·Titanium oxide fine particles 1 6.0 parts Next, the above materials were put into a SUPERMIXER PICCOLO SMP-2 (manufactured by Kawata Corporation), and mixed at 3000 rpm for 10 minutes while keeping the temperature inside the tank at 20°C by putting cold water at 20°C into the jacket. After that, the mixture was sieved through a mesh with 150 μm openings to obtain Toner 2. Details of each fine particle are shown in Table 5, and the physical properties of Toner 2 are shown in Table 6.
[0155] [Table 5]
[0156] <Toner 3, 5, 7-12, 14-18> In the production example of toner 2, except that the combination of toner particles and each fine particle was changed to that shown in Table 6, the same procedure as in the production example of toner 2 was carried out to obtain toners 3, 5, 7 to 12, and 14 to 18. For the toner not having silica fine particles 1, the step of mixing while heating to 45° C. was not carried out. Table 6 shows the physical property values of toners 3, 5, 7 to 12, and 14 to 18.
[0157] [Table 6] In the table, 2.9E+13 is 2.9 x 10 13 This indicates that.
[0158] <Production example of developing roller> <Developing roller DR1> [Formation of elastic layers (Dd1, Dd2)] The mandrel was made of a SUS Φ6 core bar that was nickel-plated and then coated with and baked a primer (product name DY39-012, manufactured by Dow Toray Co., Ltd.) The obtained mandrel was placed concentrically in a cylindrical mold having an inner diameter of 11.5 mm. The material for the elastic layer was an addition type silicone rubber composition prepared by mixing the following materials using a trimix method, and the mixture was poured into a mold heated to a temperature of 115°C. 100 parts of liquid dimethylpolysiloxane with two or more silicon-bonded alkenyl groups in one molecule (product name: DMS-V41, manufactured by Gelest) 5 parts of dimethylpolysiloxane having two or more silicon-bonded hydrogen atoms in one molecule (trade name: HMS-151, manufactured by Gelest) Platinum catalyst (product name: SIP6832.2, manufactured by Gelest) 0.048 parts Carbon black (product name: Toka Black #7360SB, manufactured by Tokai Carbon Co., Ltd.) 18 copies 20 parts of quartz (product name: Y-60, manufactured by Tatsumori Co., Ltd.) After the material was injected, it was heated and molded at a temperature of 120° C. for 10 minutes, cooled to room temperature, and then removed from the mold to obtain an elastic layer Dd1 integrated with the conductive substrate. Moreover, an elastic layer Dd2 was formed in the same manner as the elastic layer Dd1 described above, except that the amount of carbon black used was changed to 12 parts.
[0159] [Creating conductive paint (DT1, DT2)] 100 parts of a polyol compound (product name: Polytetramethylene glycol PTG1000SN, manufactured by Hodogaya Chemical Co., Ltd.) was mixed in stages with 23 parts of an isocyanate compound (product name: Millionate MT, manufactured by Tosoh Corporation) in a methyl ethyl ketone solvent, and the mixture was allowed to react for 7 hours at 80°C under a nitrogen atmosphere to obtain a polyurethane polyol A having a weight average molecular weight Mw = 11,000 and a hydroxyl value of 20 mgKOH / g. Next, under a nitrogen atmosphere, 100 parts of polypropylene glycol (trade name: Sannix PP-400, manufactured by Sanyo Chemical Industries, Ltd.) having a number average molecular weight of 400 was reacted with 43 parts of an isocyanate compound (trade name: Millionate MR-100, manufactured by Tosoh Corporation) by heating at 90°C for 2 hours, and then methyl ethyl ketone was added so that the solid content was 70%. At this time, the NCO% per solid content was 4 mass%. Then, under the condition of a reactant temperature of 50°C, 14 parts of methyl ethyl ketone oxime (manufactured by Tokyo Chemical Industries, Ltd.) was added dropwise to obtain a blocked polyisocyanate B. Block polyisocyanate B was mixed with polyurethane polyol A so that the NCO / OH group ratio was 1.4. 30 parts of carbon black (product name: MA11, manufactured by Mitsubishi Chemical Corporation) was mixed with 100 parts of resin solids, and dissolved and mixed in methyl ethyl ketone so that the total solids ratio was 30 mass %, and uniformly dispersed with a sand mill to prepare a conductive paint (DT1). Block polyisocyanate B was mixed with polyurethane polyol A so that the NCO / OH group ratio was 1.4. Carbon black (product name MA11, manufactured by Mitsubishi Chemical Corporation) was mixed at 30 parts per 100 parts of resin solids, and Art Pearl C400 transparent (manufactured by Negami Chemical Industries Co., Ltd.) was mixed at 20 parts per 100 parts of resin solids. These were dissolved and mixed in methyl ethyl ketone so that the total solids ratio was 30 mass%, and the mixture was uniformly dispersed with a sand mill to prepare a conductive paint (DT2).
[0160] [Formation of conductive elastic layers (DD1 to DD3)] The conductive resin layer-forming paint DT1 was applied onto the elastic layer Dd1 by dip coating, then dried and heat-treated at 170° C. for 1.5 hours to form a conductive elastic layer DD1. Similarly, the conductive resin layer-forming paint DT1 was dip-coated onto the elastic layer Dd2 to form a conductive elastic layer DD2. Similarly, the conductive resin layer-forming paint DT2 was dip-coated onto the elastic layer Dd1 to form a conductive elastic layer DD3.
[0161] [Preparation of surface layer paint ZT1] 17.63 g of methyltriethoxysilane (Tokyo Chemical Industry Co., Ltd.), 46.23 g of ethanol, and 3.90 g of ion-exchanged water were weighed into a 100 mL glass container. After stirring to obtain a homogeneous solution, bis(2,4-pentanedionato)bis(2-propanoate) was added. Titanium(IV) 75% isopropyl alcohol solution (Tokyo Chemical Industry Co., Ltd.) The resulting solution was refluxed for 3 hours to prepare surface layer forming paint ZT1.
[0162] [Manufacture of developing rollers DR1, DR2, and DR4] The surface layer forming paint ZT1 is ring-coated (total amount dispensed: 0.100 ml, ring speed: 85 mm / s) on the conductive elastic layer DD1 prepared earlier, and then heated at 90°C for 1 hour. By treating the conductive elastic layer, a surface layer was formed on the conductive elastic layer, thereby manufacturing the developing roller DR1. Similarly, the surface layer forming coating material ZT1 was ring-coated on the conductive elastic layer DD2, followed by heat treatment to produce a developing roller DR2. The conductive elastic layer DD3 was evaluated as it was, without forming a surface layer, as DR4.
[0163] [Developing roller DR3] A developing roller mounted on a commercially available toner cartridge 318 (cyan) (manufactured by Canon) was used as the developing roller DR3 as it was.
[0164] [Table 7] In the table, 3.0E+07 is 3.0 x 10 7 This indicates that.
[0165] <Examples 1 to 17 and Comparative Examples 1 to 8> Using the above toners 1 to 18 and developing rollers DR1 to DR4, evaluation was performed in the combinations shown in Table 9. The evaluation results are shown in Table 8.
[0166] The evaluation method and evaluation criteria are explained below. The image forming device is a commercially available laser printer, LBP-7600C (Canon A modified machine manufactured by FUJIFILM was used. Modifications included connecting to an external high voltage power source, allowing any potential difference to be set between the charging blade and the charging roller, and setting the process speed to 120 mm / sec. The process cartridge used was a commercially available toner cartridge 318 (cyan) (manufactured by Canon). The product toner and product developing roller were removed from the inside of the cartridge and cleaned with an air blower, after which 50 g of the toner to be evaluated was filled and the developing roller to be evaluated was attached. In addition, the product toner was removed from each of the yellow, magenta and black stations, and the evaluation was performed by inserting yellow, magenta and black cartridges with the toner remaining amount detection mechanism disabled.
[0167] <Evaluation of charge retention> The above process cartridge, the above modified laser printer, and evaluation paper (GF-C081 (Canon) A4: 81.4 g / m 2 ) was left to stand in a high temperature and high humidity environment (30°C / 80% RH, hereinafter referred to as H / H environment) for 48 hours. The potential difference between the charging blade and the charging roller was set to -400 V, and 10 all-white images were output, followed by one all-black image. The device was stopped during development from the developing roller to the photosensitive drum, the process cartridge was removed from the main body, and the charge amount of the toner on the developing roller before development was measured using a charge amount distribution measuring device, E-Spart Analyzer EST-1 (manufactured by Hosokawa Micron Corporation). Thereafter, one all-black image was output in the same manner, and when the image was transferred from the photosensitive drum to the intermediate transfer belt, the device was stopped and the charge amount of the toner on the intermediate transfer belt was measured in the same manner. The charge retention was evaluated according to the following criteria based on the difference between the charge amount on the developing roller and the charge amount on the intermediate transfer belt. In this evaluation, the smaller the difference in charge amount, the greater the charge retention in the image formation process. It has small attenuation and excellent charge retention. -Charge retention A: The difference in charge is 2 (μC / g) or less B: The difference in charge is more than 2 (μC / g) and less than 5 (μC / g) C: The difference in charge is more than 5 (μC / g) and less than 10 (μC / g) D: The difference in charge amount exceeds 10 (μC / g)
[0168] <Evaluation of charge build-up> The above process cartridge, the above modified laser printer, and evaluation paper (GF-C081 (Canon) A4: 81.4 g / m 2 ) was left to stand in a low temperature and low humidity environment (15°C / 10% RH, hereafter referred to as L / L environment) for 48 hours. The potential difference between the charging blade and the charging roller was set to -400 V, and one all-white image was output. During image formation, the device was stopped, the process cartridge was removed from the main body, and the charge amount of the toner on the developing roller was measured using a charge amount distribution measuring device, E-Spart Analyzer EST-1 (manufactured by Hosokawa Micron Corporation). Next, one all-white image was output under the same conditions. The device was stopped during image formation, the process cartridge was removed from the main body, and the charge amount of the toner on the developing roller was measured using a charge amount distribution measuring device, E-Spart Analyzer EST-1 (manufactured by Hosokawa Micron Corporation). The charge rise property was evaluated according to the following criteria from the difference between the charge amount of the first and second times. In this evaluation, the smaller the difference in charge amount, the better the charge rise property. -Charge start-up property A: The difference in charge is 2 (μC / g) or less B: The difference in charge is more than 2 (μC / g) and less than 5 (μC / g) C: The difference in charge is more than 5 (μC / g) and less than 10 (μC / g) D: The difference in charge amount exceeds 10 (μC / g)
[0169] <Evaluation of charge distribution> The above process cartridge, the above modified laser printer, and evaluation paper (GF-C081 (Canon) A4: 81.4 g / m 2 ) was left to stand in a low temperature and low humidity environment (15°C / 10% RH, hereafter referred to as L / L environment) for 48 hours. The potential difference between the charging blade and the charging roller was set to 0 V, and one all-white image was output. The device was stopped during image formation, the process cartridge was removed from the main body, and the charge distribution of the toner on the developing roller was measured using a charge distribution measuring device, E-Spart Analyzer EST-1 (manufactured by Hosokawa Micron Corporation). The charge distribution at this time corresponds to the charge distribution due to frictional charging. Next, the potential difference between the charging blade and the charging roller was set to -400V, and one all-white image was output. The device was stopped during image formation, the process cartridge was removed from the main body, and the charge distribution of the toner on the developing roller was measured using a charge distribution measuring device, E-Spart Analyzer EST-1 (manufactured by Hosokawa Micron Corporation). The charge distribution at this time corresponds to the charge distribution due to the superposition of frictional charging and injection charging. The half-width of the charge amount distribution when the potential difference was -400 V and when the potential difference was 0 V was compared, and since it is believed that the larger the difference, the more effective it is at sharpening the charge amount distribution by injection charging, the charge amount distribution was evaluated using as the standard how many times the half-width when the potential difference was -400 V as the half-width when the potential difference was 0 V. Charge distribution A: 0.60 times or less B: More than 0.60 times and less than 0.70 times C: More than 0.70 times and less than 0.90 times D: More than 0.90 times
[0170] <Durability evaluation> The above process cartridge, the above modified laser printer, and evaluation paper (GF-C081 (Canon) A4: 81.4 g / m 2 ) was left to stand in a normal temperature and humidity environment (23°C / 50% RH, hereinafter, N / N environment) for 48 hours. The potential difference between the charging blade and the charging roller was set to -400 V, and one all-white image was output. During image formation, the device was stopped, the process cartridge was removed from the main body, and the charge amount of the toner on the developing roller was measured using a charge amount distribution measuring device, E-Spart Analyzer EST-1 (manufactured by Hosokawa Micron Corporation). After that, 1000 images with a printing rate of 2% were output. Then, one all-white image was output. The device was stopped during image formation, the process cartridge was removed from the main body, and the charge amount of the toner on the developing roller was measured using a charge amount distribution measuring device, E-Spart Analyzer EST-1 (manufactured by Hosokawa Micron Corporation). Durability was evaluated according to the following criteria based on the difference in charge amount between the initial state and after output of 1000 sheets. ·Durability A: Change in charge is 5 (μC / g) or less B: The change in charge is greater than 5 (μC / g) and less than 10 (μC / g) C: The change in charge is greater than 10 (μC / g) and less than 20 (μC / g) D: The change in charge exceeds 20 (μC / g)
[0171] [Table 8] In the table, 5.8.E-03 is 5.8 x 10 -3 This indicates that. [Explanation of symbols]
[0172] 10 process cartridge, 11 photosensitive drum, 12 charging roller, 20 developing device, 21 developing container, 23 developing roller, 24 peeling roller, 25 regulating blade, 26 toner storage section, 27 toner leakage prevention sheet, T toner
Claims
1. A developing device including a toner, a toner carrier that carries the toner, and a toner regulating member that contacts the toner carrier and regulates the toner carried by the toner carrier, the toner carrier has a core metal, The volume resistivity of the toner determined by impedance measurement is 1.0×10 10 Ω・cm or more 1.0×10 14 Ω cm or less, In the toner carrier, a plurality of elementary processes are observed in impedance measurement between the core metal and the surface of the toner carrier using a measurement electrode having a diameter of 0.65 mm, The volume resistance Rdr between the toner carrier surface and the core metal per unit area is 5.0×10 5 Ω / cm 2 Above 2.0 x 10 8 Ω / cm 2 is as follows: The electrostatic capacitance Cdr between the toner carrier surface and the core metal per unit area is 300 pF / cm 2 900 pF / cm or more 2 is as follows: The capacitance per unit area of the toner, which is calculated from the volume resistivity and dielectric constant of the toner obtained by impedance measurement using a measurement electrode with a diameter of 10 mm, using a parallel plate capacitor model with a thickness 1.5 times the weight average particle diameter D4 of the toner obtained by the electrical detection zone method, is defined as Ctn (pF / cm 2 ), and the volume resistance per unit area of the toner is Rtn (Ω / cm 2 ) and A developing device satisfying the following formulas (1) and (2): 1.5≦(Cdr / Ctn)≦4.5 (1) 1.0×10 -4 ≦(Rdr / Rtn)≦ 1.0 ・・・(2)
2. The volume resistivity of the toner determined by impedance measurement is 1×10 11 Ω・cm or more 1×10 14 2. The developing device according to claim 1, wherein the resistivity is Ω·cm or less.
3. the toner comprises toner particles; 3. The developing device according to claim 1, wherein said toner particles have an organosilicon polymer on the surface thereof.
4. the organosilicon polymer forms a shell; 4. The developing device according to claim 3, wherein the toner particles have a toner base particle and the shell on the surface of the toner base particle.
5. 5. The developing device according to claim 3, wherein the toner has a polyvalent acid metal salt on the surface of the toner particles.
6. 6. The developing apparatus according to claim 5, wherein the polyvalent metal salt comprises a metal phosphate.
7. 7. The developing device according to claim 1, wherein the toner carrier has a surface layer having an organosilicon polymer on its outermost surface.
8. the toner comprises toner particles; the toner particles have an organosilicon polymer on their surface; 8. The developing device according to claim 1, wherein the toner carrier has an organosilicon polymer on its outermost surface.
9. 9. The developing device according to claim 1, wherein the number of the elementary processes is two.
Citation Information
Patent Citations
Developing unit and image forming device using it
JP2005331782A
toner
JP2007206378A
Single component toner and image forming method
JP2008058874A
Developing device, image forming apparatus, and process cartridge
JP2013137534A
